The Arlington study of healthy aging: a multidisciplinary community cohort study of functional decline with age - Delaney L. Davis; Rajvi Shah; Logan Pixler; Dang M. Mai; Juliana Santos; Camille Chandler; Kendall White; Jennifer Nguyen; Ario S. Moradi; Javed Choudhari; Carrie Arena-Marshall; Chase Johnson; et al. (GeroScience, 2026)

Maternal Exposure to Essential and Non-Essential Metals and Thyroid Hormone Status in a Canadian Pregnancy Cohort - Munawar Hussain Soomro; Gillian England-Mason; Catherine J. Field; Amy M. MacDonald; David W. Kinniburgh; Jonathan W. Martin; Deborah Dewey (Environmental Research, 2026)

The effects of anabolic-androgenic steroid use and training style on myogenic expression in trained male iron sport athletes - Luke M. Pelton; Nicholas J. Coker; Elizabeth M. Mullin; Jennifer B. Fields (European Journal of Applied Physiology, 2026)

Carbon Fluxes of Contrasting Degraded Peatland Pilot Sites During Early-stage Restoration: Ex-milled Bare Peat and Grazed Grassland Conversion - Anna T. Keightley; Christopher D. Field; Michael Longden; Simon J. M. Caporn (Environmental Management, 2026)
The recovery of degraded peatlands can make significant contributions to reducing greenhouse gas emissions and climate warming. This study examines restoration techniques on shallow ex-milled peatland and intensively grazed pasture on deeper peat, both subject to prior drainage. Carbon greenhouse gases (GHGs) were monitored for 3 years following restoration treatment. After drainage-blocking measures, the ex-milled peatland was ‘companion planted’ with Eriophorum species and Sphagnum . The carbon balance was highly dependent on plant age and condition, with a high CO 2 equivalent (CO 2 e) uptake when plants were vigorously growing (year 1: −22.4 ± 32.9 t CO 2 e ha −1 yr −1 ), and high emission when plants were mature and in various stages of senescence (year 2: 26.1 ± 26.4 and year 3: 16.4 ± 9.7 t CO 2 e ha −1 yr −1 ). Bare peat controls had a mean emission of 6.21 ± 1.68 t CO 2 e ha −1 yr −1 over the study period. At the other site, the grazed pasture was stripped, the bare surface planted with Sphagnum plugs, and irrigation was intensively managed via bunding, ditches, and automatic water pumping. Carbon GHG emissions were significantly reduced on this ‘carbon farm’ (2.77 ± 0.95 t CO 2 e ha −1 yr −1 ) compared to a neighbouring drained, grazed pasture control (31.7 ± 10.3 t CO 2 e ha −1 yr −1 ) over the study period (mean ± SD throughout). It appears clear that the cyclical nature of Eriophorum plant growth may only deliver carbon benefits on shallow peat over the long term if groundwater levels can be adequately supported and if climatic conditions are favourable. Conversion of grazed pasture to wetter farming crops, such as Sphagnum , can potentially deliver immediate carbon benefits, although, in this pilot, any potential loss of CO 2 e due to degraded topsoil removal, creation of bunds and irrigation ditches was not accounted for.

Using herd frailty estimates from survival models in a mortality-based syndromic surveillance system - Jaden M. Carlson; T. Brendan Murphy; Luke O’Grady; Jonas Brock; Maria P. Guelbenzu-Gonzalo; David A. Graham; Guy McGrath; Jamie A. Tratalos; Rafael de Andrade Moral; Niamh Mimnagh; Niamh L. Field; John F. Mee; et al. (Preventive Veterinary Medicine, 2026)

Conservation genomics of the imperiled Leon springs pupfish, Cyprinodon bovinus, across temporal and spatial scales - Robert J. Bretzing-Tungate; Kevin W. Conway; Megan G. Bean; Ryan K. Smith; Christopher M. Hollenbeck; Andrew T. Fields; Elizabeth P. Dolan; Steven M. Mussmann; David S. Portnoy (Conservation Genetics, 2026)
The Leon Springs pupfish, Cyprinodon bovinus , is federally listed as endangered and currently confined to spring-fed pools on the Diamond Y Spring Preserve in Pecos County, Texas, USA. A refuge population is maintained by U.S. Fish and Wildlife Service in Dexter, New Mexico, USA because of ongoing threats from hybridization with the introduced congener, the sheepshead minnow, C. variegatus. To inform continued conservation and management planning for this species, a comprehensive conservation genomics study using double digest restriction-site associated DNA sequencing was performed. No evidence of contemporary hybridization or recent introgression between C. bovinus and C. variegatus was found. The refuge population was significantly differentiated from wild samples collected at two locations, and the two wild populations (less than 1 km apart) also exhibited significant heterogeneity in allele frequencies. Estimates of within population diversity were smaller for wild locations than the refuge population. Correspondingly, the wild populations’ contemporary effective population size estimates were smaller than the refuge’s effective population size estimates (145–262 versus 679). Temporal analyses, involving genetic data collected from samples obtained in 2013, suggest an increased magnitude of drift acting on the wild populations relative to the reserve population. Based on the results of this study, it appears that steps taken in the early 2000s to eradicate genetically admixed individuals from the wild populations were successful. However, habitat fragmentation and small effective population sizes of the wild populations have led to accelerated drift and decreasing levels of within population genetic diversity. This may jeopardize the long-term persistence of C. bovinus .

Increasing Prostate Cancer Education and Screening for Black Men in Southeastern Michigan: Your Prostate, Your Health - Shane A. Tinsley; Doreen Dankerlui; Camille Romain; Wilma Ruffin; Eric Brown; Clarence Burnett; Donna Long; Karen Yacobucci; Jaye Clement; Abisola Fasakin; Biola Makinde-Odusola; Eric Williams; et al. (Journal of Cancer Education, 2025)

Putting Structural Variants Into Practice: The Role of Chromosomal Inversions in the Management of Marine Environments - Nadja M. Schneller; Jan M. Strugnell; Matt A. Field; Kerstin Johannesson; Ira Cooke (Molecular Ecology, 2025)
Major threats to marine species and ecosystems include overfishing, invasive species, pollution and climate change. The changing climate not only imposes direct threats through the impacts of severe marine heatwaves, cyclones and ocean acidification but also complicates fisheries and invasive species management by driving species range shifts. The dynamic nature of these threats means that the future of our oceans will depend on the ability of species to adapt. This has led to calls for genetic interventions focussed on enhancing species' adaptive capacity, including translocations, restocking and selective breeding. Assessing the benefits and risks of such approaches requires an improved understanding of the genetic architecture of adaptive variation, not only in relation to climate‐resilient phenotypes but also locally adapted populations and the fitness of hybrids. Large structural genetic variants such as chromosomal inversions play an important role in local adaptation by linking multiple adaptive loci. Consequently, inversions are likely to be particularly important when managing for adaptive capacity. However, under some circumstances, they also accumulate deleterious mutations, potentially increasing the risk of inbreeding depression. Genetic management that takes account of these dual roles on fitness is likely to be more effective at ensuring population persistence. We summarise evolutionary factors influencing adaptive and deleterious variation of inversions, review inversions found in marine taxa, and provide a framework to predict the consequences of ignoring inversions in key management scenarios. We conclude by describing practical methods to bridge the gap between evolutionary theory and practical application of inversions in conservation.

Biosecurity investment impacts on highly pathogenic avian influenza control in United States commercial turkey operations - Jada M. Thompson; Kelly Patyk; Victoria Fields; Matthew Branan; Amy Delgado; Kylie Roesler (Preventive Veterinary Medicine, 2025)

We Need the Largest Experiments on Earth to Achieve Our Climate Targets - Bronson W. Griscom; Susan C. Cook‐Patton; Erin Sills; Kelsey Jack; Thomas W. Crowther; Sebastien Costedoat; Christopher Field; David Hole; Lisa M. McCullough; Subhrendu K. Pattanayak; Sassan Saatchi; Will R. Turner (Global Change Biology, 2025)

Mapping the pangenome of sulfate reducing bacteria: core genes, plasticity, and novel functions in Desulfovibrio spp. - Shailabh Rauniyar; Dipayan Samanta; Payal Thakur; Priya Saxena; Ram N. Singh; Adelme Bazin; Alain Bomgni; Ernest Fotseu; Gnimpieba Z. Etienne; Venkata Gadhamshetty; Brent M. Peyton; Matthew Fields; et al. (World Journal of Microbiology and Biotechnology, 2025)

Novel geopolymer materials for fast and thermal neutron shielding - Jianxin Zhou; Alexander Fields; Shaffer Bauer; Ali Ozer; Waltraud M. Kriven; Angela Di Fulvio (Annals of Nuclear Energy, 2025)

Conservation benefits of a large marine protected area network that spans multiple ecosystems - Joshua G. Smith; Cori Lopazanski; Christopher M. Free; Julien Brun; Clarissa Anderson; Mark H. Carr; Joachim Claudet; Jenifer E. Dugan; Jacob G. Eurich; Tessa B. Francis; David A. Gill; Scott L. Hamilton; et al. (Conservation Biology, 2025)
Marine protected areas (MPAs) are widely implemented tools for long‐term ocean conservation and resource management. Assessments of MPA performance have largely focused on specific ecosystems individually and have rarely evaluated performance across multiple ecosystems either in an individual MPA or across an MPA network. We evaluated the conservation performance of 59 MPAs in California's large MPA network, which encompasses 4 primary ecosystems (surf zone, kelp forest, shallow reef, deep reef) and 4 bioregions, and identified MPA attributes that best explain performance. Using a meta‐analytic framework, we evaluated the ability of MPAs to conserve fish biomass, richness, and diversity. At the scale of the network and for 3 of 4 regions, the biomass of species targeted by fishing was positively associated with the level of regulatory protection and was greater inside no‐take MPAs, whereas species not targeted by fishing had similar biomass in MPAs and areas open to fishing. In contrast, species richness and diversity were not as strongly enhanced by MPA protection. The key features of conservation effectiveness included MPA age, preimplementation fisheries pressure, and habitat diversity. Important drivers of MPA effectiveness for single MPAs were consistent across MPAs in the network, spanning regions and ecosystems. With international targets aimed at protecting 30% of the world's oceans by 2030, MPA design and assessment frameworks should consider conservation performance at multiple ecologically relevant scales, from individual MPAs to MPA networks.

Comprehensive Characterisation of the RFC1 Repeat in an Australian Cohort - Kayli C. Davies; Haloom Rafehi; Liam G. Fearnley; Penny Snell; Greta Gillies; Tess A. Field; Gábor M. Halmágyi; Kishore R. Kumar; Kate Pope; Renee Smyth; Susan E. Tomlinson; Stephen Tisch; et al. (The Cerebellum, 2025)

Feedback From Pregnant Women With Gestational Diabetes on a Proposed Lifestyle Intervention - Molly E. Waring; Katherine E. McManus-Shipp; Christiana M. Field; Sophia A. Gaspard; Linda S. Pescatello; Ock K. Chun; Ava Holland; Vanessa Sena; Helen Wu; Kristen Annis-Brayne; Andrea D. Shields (Journal of Nutrition Education and Behavior, 2025)

Deep-time history of primate behavior and ecology as revealed by ancestral state reconstructions - Jeffrey K. Spear; Eva A. Hoffman; Juri A. Miyamae; Christopher D. Whalen; Alyssa M. Arre; Chloe Chen-Kraus; Margaret K. Corley; Matteo Fabbri; Jacques A. Gauthier; Michael Hanson; Amanda Leiss; Nicolás Mongiardino Koch; et al. (Journal of Mammalian Evolution, 2025)

Towards environmental justice: A framework and strategic approach for implementing community based participatory research in the earth and environmental sciences - Alexis M. Wilson; Emily Polk; Christopher B. Field; Scott Fendorf (Environmental Science & Policy, 2025)

Springtime upwelling conditions influence microbial communities and dissolved thiamin compounds in the California Current Ecosystem - Kelly C. Shannon; Gillian St. John; Robin Gould; Christopher Hartzell; Hailey Matthews; Elizabeth J. Brennan; Luis M. Bolaños; Steven T. Lindley; John C. Field; Nate Mantua; Rachel Johnson; Carson Jeffres; et al. (Limnology and Oceanography, 2025)
Understanding dissolved concentrations of the essential coenzyme thiamin (vitamin B 1 ) can provide insights into the biological controls on highly productive upwelling systems such as the California Current Ecosystem. To connect thiamin availability with microbial communities in the California Current Ecosystem, we measured concentrations of dissolved thiamin and its biochemically related moieties (thiamin congeners) and 16S rRNA gene‐based microbial communities during the spring. We found that strong upwelling caused a depletion of dissolved thiamin precursor compounds and abiotic degradation products relative to periods of weak upwelling. Specific microbial taxa, including species of SAR11 ecotypes, Candidatus Nitrosopumilus, and SUP05 cluster, were also significantly enriched with strong upwelling. Our data provide evidence that alterations to microbial communities in the mixed layer that occur as a result of upwelling could constrain the availability of dissolved thiamin and its chemical congeners in the California Current Ecosystem.

Penguin guano suppresses the grazing rate and modifies swimming behavior in Antarctic Krill (Euphausia superba) - Nicole Hellessey; Marc Weissburg; David M. Fields (Frontiers in Marine Science, 2025)
Antarctic krill ( Euphausia superba ) are a key component of the Antarctic ecosystem linking primary and some secondary production to higher trophic levels including fish, penguins, seals, and whales. Understanding their response to environmental stimuli therefore provides insights into the trophic ecology of Antarctic systems. This laboratory study quantified the influence of penguin guano, a presumptive predator cue, chlorophyll concentration and flow speed on krill swimming behavior. In addition, ingestion rates with and without guano were measured. Such inquiries are necessary to determine if predator risk cues modify krill activities in ways that have consequences for other members of the Antarctic trophic web. Krill often exhibited acute turns when guano was present and varied their swimming speeds more when guano was present. These are both indicators of avoidance behavior to the negative chemical cues represented by penguin guano. Similarly, krill’s ingestion rates dropped significantly for a prolonged period of time in the presence of guano. This decrease in feeding will have impacts on krill’s nutritional value to their predators, prey uptake rates (prey survival) and the sequestration of carbon to the deep ocean as krill decrease their defecation rates. This study supports the hypothesis that krill use chemical signals to detect and behaviorally respond to food and predation risk.

Assessing South Africa’s marine protected area quality and progress towards conservation goals: An application of The MPA Guide framework - Laurel C. Field; Kendyl Wright; Jenna Sullivan-Stack; Jean M. Harris; Stephen P. Kirkman; Peter J. Fielding; Ané Oosthuizen; Siyabonga Dlulisa; Anastasiya Laznya; Emanuel J. Gonçalves; Kirsten Grorud-Colvert (Marine Policy, 2025)

Assessment of genomic diversity within and between two cryptic shiners, the West Texas shiner ( Notropis megalops ) and the Texas shiner ( Notropis amabilis ) - Kayla R. Dye; Andrew T. Fields; Megan G. Bean; Sarah M. Robertson; Christopher M. Hollenbeck; Kevin W. Conway; David S. Portnoy (Journal of Fish Biology, 2025)
The presence of cryptic species can hinder effective conservation planning and implementation, as has been the case for speciose groups of freshwater fishes that are difficult to differentiate due to conserved morphologies. The West Texas shiner Notropis megalops and the Texas shiner Notropis amabilis are a cryptic pair of leuciscids (minnows) that co‐occur in spring‐fed tributaries of the Rio Grande in Texas and Mexico. Both N. megalops and N. amabilis are listed as Species of Greatest Conservation Need by the Texas Parks and Wildlife Department. Notropis amabilis is widespread and listed as apparently secure by Texas Parks and Wildlife Department whereas N. megalops has a very limited distribution and has not been ranked by Texas Parks and Wildlife Department because of data deficiency. Morphological differences between these species have been described; however, proper identification in situ remains problematic. Furthermore, given their range of overlap there is potential for hybridization, and limited genetic data have been collected comparing the species. Therefore, reduced representation genomic and mitochondrial sequencing data were used to reassess the distinctness of the species, screen for hybridization, and characterize their relative frequencies throughout their range of overlap. Genomic analyses recovered two distinct genetic groups corresponding to the species ( F' CT = 0.89) with no evidence of admixture or introgression. The species were found to co‐occur at three sampling locations, two in the Devils River and one in the Pecos, but not in equal frequencies. Overall, these results provide data and tools for further research on N. megalops needed for accurate conservation policies and management practices.

A Palearctic view of a bat fungal disease - F. Whiting‐Fawcett; A. S. Blomberg; T. Troitsky; M. B. Meierhofer; K. A. Field; S. J. Puechmaille; T. M. Lilley (Conservation Biology, 2025)
The fungal infection causing white‐nose disease in hibernating bats in North America has resulted in dramatic population declines of affected species, since the introduction of the causative agent Pseudogymnoascus destructans . The fungus is native to the Palearctic, where it also infects several bat species, yet rarely causes severe pathology or the death of the host. Pseudogymnoascus destructans infects bats during hibernation by invading and digesting the skin tissue, resulting in the disruption of torpor patterns and consequent emaciation. Relations among pathogen, host, and environment are complex, and individuals, populations, and species respond to the fungal pathogen in different ways. For example, the Nearctic Myotis lucifugus responds to infection by mounting a robust immune response, leading to immunopathology often contributing to mortality. In contrast, the Palearctic M. myotis shows no significant immunological response to infection. This lack of a strong response, resulting from the long coevolution between the hosts and the pathogen in the pathogen's native range, likely contributes to survival in tolerant species. After more than 15 years since the initial introduction of the fungus to North America, some of the affected populations are showing signs of recovery, suggesting that the fungus, hosts, or both are undergoing processes that may eventually lead to coexistence. The suggested or implemented management methods of the disease in North America have encompassed, for example, the use of probiotics and fungicides, vaccinations, and modifying the environmental conditions of the hibernation sites to limit the growth of the pathogen, intensity of infection, or the hosts’ responses to it. Based on current knowledge from Eurasia, policy makers and conservation managers should refrain from disrupting the ongoing evolutionary processes and adopt a holistic approach to managing the epizootic.

Klebsiella pneumoniae in stranded California sea lions (Zalophus californianus) of Central California between 2017-2022 - Sydney N. Zotto; Robin C. Dunkin; Juliana D. Limon; Maia S. Smith; Lisabet M. Hortensius; Margaret E. Martinez; Pádraig J. Duignan; Cara Field; Esteban Soto; Dane Whitaker; Carlos Rios; Maurice Byukusenge; et al. (Frontiers in Marine Science, 2025)
Klebsiella pneumoniae is a Gram-negative, facultative anaerobic, and non-motile bacillus frequently observed in mammals. A hypermucoviscous (HMV) phenotype of K. pneumoniae is reported in stranded California sea lions (CSL) causing pleuritis and bronchopneumonia as a persistent cause of strandings. We describe an increase in cases of HMV and non-HMV K. pneumoniae in stranded CSLs along the California coast between 2017 to 2022. 2,146 live-stranded CSLs were rescued by The Marine Mammal Center (Sausalito, California). 47 of these tested positive for K. pneumoniae , with a rise in annual incidence from 0.92% (3/331) in 2017 to 8.5% (14/165) and 7.2% (23/320) in 2021 and 2022, respectively. These strandings occurred across 965 kilometers along the North-Central California coast from Bodega Bay, Sonoma, to Avila Beach, San Luis Obispo. A similar pattern was observed in beach-cast CSL carcasses by the Long Marine Laboratory (LML) Stranding Network in Santa Cruz, California who had 8 CSLs test positive for K. pneumoniae with an annual incidence rate of 2.0% (1/50) and 10.1% (7/69) in 2021 and 2022, respectively, with no cases reported prior to 2021. We applied whole-genome sequencing (WGS) to 8 isolates obtained by LML in 2022. WGS analysis revealed high nucleotide similarity between any pair of isolates. Multilocus Sequence Typing showed that all isolates belonged to Sequence type 65 and contained the K2 polysaccharide capsule and siderophore aerobactin, which are all characteristics of hypervirulent K. pneumoniae. We discuss possible causes for this trend and a need for research on K. pneumoniae in free-ranging CSLs in California.

Larval ontogeny enhances resilience to a patchy planktonic food supply in the American lobster (Homarus americanus) - Evelyn M. Layland; Emily Patrick; Molly Spencer; Rachel Lasley-Rasher; David M. Fields; Richard A. Wahle (Fisheries Research, 2025)

One size does not fit all: Intra– and interspecific variation of den site use in two marsupial glider species in fragmented forest - Christopher M. McLean; Jed Field; Samuel A.R. Hayley; Matthew Hingee; Chad T. Beranek (Forest Ecology and Management, 2025)

Assessments of expected MPA outcomes can inform and improve biodiversity conservation: Case studies using The MPA Guide - Jenna Sullivan-Stack; Gabby N. Ahmadia; Dominic A. Andradi-Brown; Alexandra Barron; Cassandra M. Brooks; Joachim Claudet; Barbara Horta e Costa; Estradivari; Laurel C. Field; Sylvaine Giakoumi; Emanuel Gonçalves; Natalie Groulx; et al. (Marine Policy, 2024)

Effects of burning on vegetation, soil physicochemistry and prokaryotic microbial communities in surface and subsurface peat - Shaun M. Allingham; Samantha J. Drake; Andrew Ramsey; Chris D. Field; Felix C. Nwaishi; David R. Elliott (Science of The Total Environment, 2024)

Uncovering the hidden world of riverbed sediments: The role of sediment heterogeneity and cross-bar channel fills in the hydrogeochemical dynamics of the hyporheic zone - Jeffery T. McGarr; Pei Li; Robert G. Ford; Teagan Kleman; Colton Fields; Julie Hobbs; Lydia Lupton; Emma Poston; Thomas Marsh; Leah Trutschel; Ken M. Fritz; Annette Rowe; et al. (Journal of Hydrology, 2024)

Bridging the spawner-recruit disconnect II: Revealing basin-scale correlations between zooplankton and lobster settlement dynamics in the Gulf of Maine - Burton Shank; Joshua T. Carloni; Paul Geoghegan; David M. Fields; Andrew G. Goode; Harvey J. Walsh; Richard A. Wahle (Fisheries Research, 2024)

Biochar-Sulfate Reducing Bacteria synergy: A green approach for antimony removal and recovery from high-concentrated waters - Marina M. Atilano-Camino; Ana P. Canizales Laborín; Angelita M. Ortega Juárez; M. Rosario Sánchez-Macías; Iván Moreno-Andrade; Reyes Sierra-Álvarez; Jim Field; Christopher Rensing; Julián Carrillo-Reyes; Francisco J. Cervantes; Aurora M. Pat-Espadas (Journal of Environmental Chemical Engineering, 2024)

Population structure of the Atlantic angel shark (Squatina dumeril) in United States waters of the western North Atlantic Ocean - Andrew T. Fields; William B. Driggers; Christian M. Jones; David S. Portnoy (Environmental Biology of Fishes, 2024)

Maternal pre-pregnancy BMI influences the associations between bisphenol and phthalate exposures and maternal weight changes and fat accumulation - Nathalie Irvine; Rhonda C. Bell; Fatheema B. Subhan; Catherine J. Field; Jiaying Liu; Amy M. MacDonald; David W. Kinniburgh; Jonathan W. Martin; Deborah Dewey; Gillian England-Mason; B.J. Kaplan; C.J. Field; et al. (Environmental Research, 2024)

Climate induced declines in maternal size may come at a cost to embryonic investment and larval performance in the American lobster - Alexander Ascher; Maura Niemisto; Donaven Baughman; Grace Andrews; Curtis Morris; Emily Patrick; Richard A. Wahle; David M. Fields (Fisheries Research, 2024)

Changes in nitrogen functional genes and microbial populations in soil profiles of a peatland under different burning regimes - Shaun M. Allingham; Samantha J. Drake; Andrew Ramsey; Chris D. Field; Felix C. Nwaishi; David R. Elliott (Applied Soil Ecology, 2024)

Chromosomal inversions harbour excess mutational load in the coral, Acropora kenti , on the Great Barrier Reef - Jia Zhang; Nadja M. Schneller; Matt A. Field; Cheong Xin Chan; David J. Miller; Jan M. Strugnell; Cynthia Riginos; Line Bay; Ira Cooke (Molecular Ecology, 2024)
The future survival of coral reefs in the Anthropocene depends on the capacity of corals to adapt as oceans warm and extreme weather events become more frequent. Targeted interventions designed to assist evolutionary processes in corals require a comprehensive understanding of the distribution and structure of standing variation, however, efforts to map genomic variation in corals have so far focussed almost exclusively on SNPs, overlooking structural variants that have been shown to drive adaptive processes in other taxa. Here, we show that the reef‐building coral, Acropora kenti , harbours at least five large, highly polymorphic structural variants, all of which exhibit signatures of strongly suppressed recombination in heterokaryotypes, a feature commonly associated with chromosomal inversions. Based on their high minor allele frequency, uniform distribution across habitats and elevated genetic load, we propose that these inversions in A . kenti are likely to be under balancing selection. An excess of SNPs with high impact on protein‐coding genes within these loci elevates their importance both as potential targets for adaptive selection and as contributors to genetic decline if coral populations become fragmented or inbred in future.

Climate and community in Central Mesa Verde - Sean Field; Donna M. Glowacki (Journal of Quaternary Science, 2024)
Periods of acute climate stress – the convergence of low subsistence yields due to poor climate conditions and ineffective buffering strategies due to climate variability – critically reduces peoples’ ability to subsist and mitigate food shortages, thereby creating conditions that could result in profound social change. Here, paleoclimate reconstructions are used to identify periods of acute stress at three large Ancestral Pueblo villages in the US Southwest. These periods are examined in relation to occupation histories at each village showing that in certain instances, acute climate stress played a primary role in people's decisions to leave communities. However, not all of the communities reacted to stress in the same way indicating that distinct patterns of climate and social context played an important role in influencing how acute climate stress was experienced by different groups. Results from this study highlight the importance of community‐specific histories when considering the impact of climate stress on past people.

Stereo-video landers can rapidly assess marine fish diversity and community assemblages - Kinsey E. Matthews; Ryan T. Fields; Kathleen P. Cieri; Jacklyn L. Mohay; Mary G. Gleason; Richard M. Starr (Frontiers in Marine Science, 2024)
Climate change and anthropogenic stressors affect the distribution, abundance, and diversity of fish communities across the world. To understand rapidly changing biotic communities, resource managers need a method to quickly and efficiently document temporal and spatial changes in community assemblages across various spatial scales. In this study, we describe the use of new video lander tools to survey fish communities in rocky marine habitats on the continental shelf and slope in California, USA. We evaluate how fish diversity metrics determined by video surveys vary among geographically distinct areas. Our results demonstrate that species diversity, evenness, and richness vary spatially across the coast. Furthermore, community assemblages differ at both broad and fine spatial scales because of differences among habitats. Length frequencies and densities of species in this study were similar to those reported in previous studies. As community assemblages and biodiversity metrics shift in response to changing stressors, it is increasingly important to develop tools and methodologies to detect and rapidly monitor these changes.

State of the California Current Ecosystem report in 2022: a tale of two La Niñas - Andrew R. Thompson; Rasmus Swalethorp; Michaela Alksne; Jarrod A. Santora; Elliott L. Hazen; Andrew Leising; Erin Satterthwaite; William J. Sydeman; Clarissa R. Anderson; Toby D. Auth; Simone Baumann-Pickering; Timothy Baumgardner; et al. (Frontiers in Marine Science, 2024)
2022 marked the third consecutive La Niña and extended the longest consecutive stretch of negative Oceanic Niño Index since 1998-2001. While physical and biological conditions in winter and spring largely adhered to prior La Niña conditions, summer and fall were very different. Similar to past La Niña events, in winter and spring coastal upwelling was either average or above average, temperature average or below average, salinity generally above average. In summer and fall, however, upwelling and temperature were generally average or slightly below average, salinity was close to average and chlorophyll a was close to average. Again, as during prior La Niña events, biomass of northern/southern copepods was above/below average off Oregon in winter, and body size of North Pacific krill in northern California was above average in winter. By contrast, later in the year the abundance of northern krill dropped off Oregon while southern copepods increased and body sizes of North Pacific krill fell in northern California. Off Oregon and Washington abundances of market squid and Pacific pompano (indicators of warm, non-typical La Niña conditions) were high. In the 20 th century, Northern anchovy recruitment tended to be high during cold conditions, but despite mostly warm conditions from 2015-2021 anchovy populations boomed and remained high in 2022. Resident seabird reproductive success, which tended in the past to increase during productive La Niña conditions was highly variable throughout the system as common murre and pelagic cormorant, experienced complete reproductive failure at Yaquina Head, Oregon while Brandt’s cormorant reproduction was average. At three sampling locations off central California, however, common murre reproduction was close to or above average while both pelagic and Brandt’s cormorant were above average. California sealion reproduction has been above average each year since 2016, and pup weight was also above average in 2022, likely in response not to La Niña or El Niño but continuous high abundance of anchovy. The highly variable and often unpredictable physical and biological conditions in 2022 highlight a growing recognition of disconnects between basin-scale indices and local conditions in the CCE. “July-December 2022 is the biggest outlier from individual “strong” La Niña (events) ever going back to the 50s.” – Nate Mantua

Development and application of a bioenergetics growth model for multiple early life stages of an ecologically important marine fish - Mark M. Morales; Jerome Fiechter; John C. Field; Neosha S Kashef; Elliott L. Hazen; Mark H. Carr (Ecological Modelling, 2024)

Assessment of oceanographic conditions during the North Atlantic EXport processes in the ocean from RemoTe sensing (EXPORTS) field campaign - Leah Johnson; David A. Siegel; Andrew F. Thompson; Erik Fields; Zachary K. Erickson; Ivona Cetinic; Craig M. Lee; Eric A. D'Asaro; Norman B. Nelson; Melissa M. Omand; Michaela Sten; Shawnee Traylor; et al. (Progress in Oceanography, 2024)

Microbial communities are indicators of parasite infection status - Kyle Swanson; April M. H. Blakeslee; Amy E. Fowler; Sara Roozbehi; Erin K. Field (Environmental Microbiology, 2023)
Growing evidence suggests that microbiomes have been shaping the evolutionary pathways of macroorganisms for millennia and that these tiny symbionts can influence, and possibly even control, species interactions like host–parasite relationships. Yet, while studies have investigated host–parasites and microbiomes separately, little has been done to understand all three groups synergistically. Here, we collected infected and uninfected Eurypanopeus depressus crab hosts from a coastal North Carolina oyster reef three times over 4 months. Infected crabs demonstrated an external stage of the rhizocephalan parasite, Loxothylacus panopaei . Community analyses revealed that microbial richness and diversity were significantly different among tissue types (uninfected crab, infected crab, parasite externae and parasite larvae) and over time (summer and fall). Specifically, the microbial communities from parasite externae and larvae had similar microbiomes that were consistent through time. Infected crabs demonstrated microbial communities spanning those of their host and parasite, while uninfected crabs showed more distinctive communities with greater variability over time. Microbial communities were also found to be indicators of early‐stage infections. Resolving the microbial community composition of a host and its parasite is an important step in understanding the microbiome's role in the host–parasite relationship and determining how this tripartite relationship impacts coevolutionary processes.

Human milk: From complex tailored nutrition to bioactive impact on child cognition and behavior - Carolina de Weerth; Anna-Katariina Aatsinki; Meghan B. Azad; Frank F. Bartol; Lars Bode; Maria Carmen Collado; Amanda M. Dettmer; Catherine J. Field; Meagan Guilfoyle; Katie Hinde; Aniko Korosi; Hellen Lustermans; et al. (Critical Reviews in Food Science and Nutrition, 2023)

Malassezia is widespread and has undescribed diversity in the marine environment - Ronja M. Steinbach; Fouad El Baidouri; Lorna M.Y. Mitchison-Field; Fang Yun Lim; Joanne Ekena; Ellysa J.D. Vogt; Amy Gladfelter; Ashleigh B. Theberge; Anthony S. Amend (Fungal Ecology, 2023)

Palaeoenvironmental history of the Middle Pleistocene deposits at Gilson, Warwickshire, England: part of the High Speed Two railway route alignment - Sebastian M. Gibson; Michael H. Field; Philip L. Gibbard (Journal of Quaternary Science, 2023)
The investigation of a hillside at Gilson (Lat. 52.510341, Long. ‐1.718313), southwest of Coleshill, Warwickshire (within the High Speed Two railway ‘Delta Junction’ compound), England, has yielded evidence of sedimentation during a temperate stage. The site's stratigraphy starts with the aggregation of cold‐climate sand and gravels deposited during the Anglian Stage within the proto‐Tame and proto‐Blythe palaeovalleys. A warm‐climate period is recorded by the infill of organic material representing the second half of the Hoxnian interglacial Stage. Picea, Abies and Pinus dominate vegetation within a swamp‐like environment, before a Pinus forest develops in the upper part of the organic sequence. The following cold‐climate period saw incision and aggregation of the surrounding region throughout much of the Wolstonian and Devensian Stages, where much of the overlying silt, sand and gravel were reworked under intense periglacial conditions. Presented here is a geophysical examination of the shallow basin by ground‐penetrating radar undertaken to understand the spatial distribution and stratigraphical history of the basin. The deposits at Gilson provide a valuable stratigraphic marker in the glacial sequence of the English West Midlands and are correlated to similar deposits at neighbouring Quinton and Nechells. At these regional sites organic accumulation occurred for most of the temperate stage, infilling lake basins. These sequences indicate an environment dominated by pollen of Abies, Quercus, Ulmus and Corylus woodland vegetation. These assemblages differ markedly from those typically found in the last interglacial and confirm correlation to the Middle Pleistocene Hoxnian interglacial Stage ( c . MIS 11c).

Sex-specific associations between maternal phthalate exposure and neurodevelopmental outcomes in children at 2 years of age in the APrON cohort - Deborah Dewey; Jonathan W. Martin; Amy M. MacDonald; David W. Kinniburgh; Nicole Letourneau; Gerald F. Giesbrecht; Catherine J. Field; Rhonda C. Bell; Gillian England-Mason (NeuroToxicology, 2023)

Philopatry influences the genetic population structure of the blacktip shark ( Carcharhinus limbatus ) at multiple spatial scales - Dominic G. Swift; Shannon J. O'Leary; R. Dean Grubbs; Bryan S. Frazier; Andrew T. Fields; Jayne M. Gardiner; J. Marcus Drymon; Dana M. Bethea; Tonya R. Wiley; David S. Portnoy (Molecular Ecology, 2023)
Understanding how interactions among microevolutionary forces generate genetic population structure of exploited species is vital to the implementation of management policies that facilitate persistence. Philopatry displayed by many coastal shark species can impact gene flow and facilitate selection, and has direct implications for the spatial scales of management. Here, genetic structure of the blacktip shark ( Carcharhinus limbatus ) was examined using a mixed‐marker approach employing mitochondrial control region sequences and 4339 SNP‐containing loci generated using ddRAD‐Seq. Genetic variation was assessed among young‐of‐the‐year sampled in 11 sites in waters of the United States in the western North Atlantic Ocean, including the Gulf of Mexico. Spatial and environmental analyses detected 68 nuclear loci putatively under selection, enabling separate assessments of neutral and adaptive genetic structure. Both mitochondrial and neutral SNP data indicated three genetically distinct units—the Atlantic, eastern Gulf, and western Gulf—that align with regional stocks and suggest regional philopatry by males and females. Heterogeneity at loci putatively under selection, associated with temperature and salinity, was observed among sites within Gulf units, suggesting local adaptation. Furthermore, five pairs of siblings were identified in the same site across timescales corresponding with female reproductive cycles. This indicates that females re‐used a site for parturition, which has the potential to facilitate the sorting of adaptive variation among neighbouring sites. The results demonstrate differential impacts of microevolutionary forces at varying spatial scales and highlight the importance of conserving essential habitats to maintain sources of adaptive variation that may buffer species against environmental change.

Long‐term elevated precipitation induces grassland soil carbon loss via microbe‐plant–soil interplay - Mengmeng Wang; Xin Sun; Baichuan Cao; Nona R. Chiariello; Kathryn M. Docherty; Christopher B. Field; Qun Gao; Jessica L. M. Gutknecht; Xue Guo; Genhe He; Bruce A. Hungate; Jiesi Lei; et al. (Global Change Biology, 2023)
Global climate models predict that the frequency and intensity of precipitation events will increase in many regions across the world. However, the biosphere‐climate feedback to elevated precipitation (eP) remains elusive. Here, we report a study on one of the longest field experiments assessing the effects of eP, alone or in combination with other climate change drivers such as elevated CO 2 (eCO 2 ), warming and nitrogen deposition. Soil total carbon (C) decreased after a decade of eP treatment, while plant root production decreased after 2 years. To explain this asynchrony, we found that the relative abundances of fungal genes associated with chitin and protein degradation increased and were positively correlated with bacteriophage genes, suggesting a potential viral shunt in C degradation. In addition, eP increased the relative abundances of microbial stress tolerance genes, which are essential for coping with environmental stressors. Microbial responses to eP were phylogenetically conserved. The effects of eP on soil total C, root production, and microbes were interactively affected by eCO 2 . Collectively, we demonstrate that long‐term eP induces soil C loss, owing to changes in microbial community composition, functional traits, root production, and soil moisture. Our study unveils an important, previously unknown biosphere‐climate feedback in Mediterranean‐type water‐limited ecosystems, namely how eP induces soil C loss via microbe‐plant–soil interplay.

Understanding trait diversity: the role of geodiversity - Grant Vernham; Joseph J. Bailey; Jonathan M. Chase; Jan Hjort; Richard Field; Franziska Schrodt (Trends in Ecology & Evolution, 2023)

Evaluating the sustainability of the 2017 US biofuel industry with an integrated techno-economic analysis and life cycle assessment - Jack P. Smith; Braden J. Limb; Colin M. Beal; Kelly R. Banta; John L. Field; Steven J. Simske; Jason C. Quinn (Journal of Cleaner Production, 2023)

Correction to: Analysing the distribution of strictly protected areas toward the EU2030 target - Roberto Cazzolla Gatti; Piero Zannini; Gianluca Piovesan; Nicola Alessi; Alberto Basset; Carl Beierkuhnlein; Michele Di Musciano; Richard Field; John M. Halley; Samuel Hoffmann; Jacopo Iaria; Athanasios Kallimanis; et al. (Biodiversity and Conservation, 2023)

Analysing the distribution of strictly protected areas toward the EU2030 target - Roberto Cazzolla Gatti; Piero Zannini; Gianluca Piovesan; Nicola Alessi; Alberto Basset; Carl Beierkuhnlein; Michele Di Musciano; Richard Field; John M. Halley; Samuel Hoffmann; Jacopo Iaria; Athanasios Kallimanis; et al. (Biodiversity and Conservation, 2023)
Protecting global biodiversity is one of the most urgent tasks for the coming decades. Area-based conservation is a pillar for preserving ecosystems and species. Strictly protected areas specifically preserve biodiversity and ecosystem processes. The “EU Biodiversity Strategy for 2030” targets strict protection for 10% of land area. Here we performed the first analysis of strictly protected areas (as IUCN type Ia, Ib, and II) across Europe, by investigating their area coverage at the level of biogeographical regions, countries and elevation gradients. We show that, with few exceptions, the amount of strictly protected area is very limited and the spatial distribution of such protected areas is biased towards higher elevation sites, as in the case of other protected areas. Then, we suggest that potential areas should be identified to expand strictly protected areas with low economic and social costs including, for instance, areas with high biodiversity value, low population, and low productive land use. Finally, we propose that a coordinated effort and a strategic plan to achieve continental-scale conservation are fundamental, and at least half of this land under strict conservation (i.e. 5%) should be under the protection categories Ia and Ib.

Age, Growth and Maturity of the Bonnethead Sphyrna tiburo in the U.S. Gulf of Mexico - Bryan S. Frazier; Elizabeth A. Vinyard; Andrew T. Fields; William B. Driggers; R. Dean Grubbs; Douglas H. Adams; J. Marcus Drymon; Jayne M. Gardiner; Jill M. Hendon; Eric Hoffmayer; Robert E. Hueter; R. J. David Wells; et al. (Environmental Biology of Fishes, 2023)

Effects of airgun discharges used in seismic surveys on development and mortality in nauplii of the copepod Acartia tonsa - Emilie Hernes Vereide; Marina Mihaljevic; Howard I. Browman; David M. Fields; Mette Dalgaard Agersted; Josefin Titelman; Karen de Jong (Environmental Pollution, 2023)

Automated detection, delineation and quantification of whole-body bone metastasis using FDG-PET/CT images - R. Nigam; M. Field; G. Harris; M. Barton; M. Carolan; P. Metcalfe; L. Holloway (Physical and Engineering Sciences in Medicine, 2023)
Non-small cell lung cancer (NSCLC) patients with the metastatic spread of disease to the bone have high morbidity and mortality. Stereotactic ablative body radiotherapy increases the progression free survival and overall survival of these patients with oligometastases. FDG-PET/CT, a functional imaging technique combining positron emission tomography (PET) with 18 F-fluorodeoxyglucose (FDG) and computer tomography (CT) provides improved staging and identification of treatment response. It is also associated with reduction in size of the radiotherapy tumour volume delineation compared with CT based contouring in radiotherapy, thus allowing for dose escalation to the target volume with lower doses to the surrounding organs at risk. FDG-PET/CT is increasingly being used for the clinical management of NSCLC patients undergoing radiotherapy and has shown high sensitivity and specificity for the detection of bone metastases in these patients. Here, we present a software tool for detection, delineation and quantification of bone metastases using FDG-PET/CT images. The tool extracts standardised uptake values (SUV) from FDG-PET images for auto-segmentation of bone lesions and calculates volume of each lesion and associated mean and maximum SUV. The tool also allows automatic statistical validation of the auto-segmented bone lesions against the manual contours of a radiation oncologist. A retrospective review of FDG-PET/CT scans of more than 30 candidate NSCLC patients was performed and nine patients with one or more metastatic bone lesions were selected for the present study. The SUV threshold prediction model was designed by splitting the cohort of patients into a subset of ‘development’ and ‘validation’ cohorts. The development cohort yielded an optimum SUV threshold of 3.0 for automatic detection of bone metastases using FDG-PET/CT images. The validity of the derived optimum SUV threshold on the validation cohort demonstrated that auto-segmented and manually contoured bone lesions showed strong concordance for volume of bone lesion ( r = 0.993) and number of detected lesions ( r = 0.996). The tool has various applications in radiotherapy, including but not limited to studies determining optimum SUV threshold for accurate and standardised delineation of bone lesions and in scientific studies utilising large patient populations for instance for investigation of the number of metastatic lesions that can be treated safety with an ablative dose of radiotherapy without exceeding the normal tissue toxicity.

Radiation Oncology Virtual Education Rotation (ROVER) 2.0 for Residents: Implementation and Outcomes - Navjot K. Sandhu; Elham Rahimy; Ryan Hutten; Utkarsh Shukla; Anne Rajkumar-Calkins; Jacob A. Miller; Rie Von Eyben; Christopher R. Deig; Jean-Pierre Obeid; Rachel B. Jimenez; Emma C. Fields; Erqi L. Pollom; et al. (Journal of Cancer Education, 2023)

A positive temperature‐dependent effect of elevated CO 2 on growth and lipid accumulation in the planktonic copepod, Calanus finmarchicus - David M. Fields; Jeffrey A. Runge; Cameron R. S. Thompson; Caroline M. F. Durif; Steven D. Shema; Reidun M. Bjelland; Maura Niemisto; Michael T. Arts; Anne Berit Skiftesvik; Howard I. Browman (Limnology and Oceanography, 2023)
Calanus finmarchicus were reared from eggs to adults at 12°C and 16°C with non‐limiting food in combination with ambient (600 μ atm) and high (1100 μ atm) p CO 2 . These conditions are likely to be encountered by the species at the southern margins of its biogeographical range by the end of the century. Dry weight (DW), carbon (C) and nitrogen (N) mass, oil‐sac volume (OSV), fatty acid composition (FA), and oxygen consumption rates (OCR) were measured on newly molted stage CV copepodites and recently molted adult females. By focusing our measurements on these precise events in the life cycle, we were able to obtain a more accurate comparison of growth and respiration across treatments. Copepods raised at 12°C had a significantly greater DW, OSV, and C and N mass than those raised at 16°C High p CO 2 , independent of temperature, was associated with a further increase in the DW and C content of the copepods. Interactive effects of temperature and p CO 2 resulted in a larger OSV at low temperature and high p CO 2 . Mass‐specific respiration rates were significantly lower at lower temperatures and elevated p CO 2 suggesting that the increase in mass (DW, C, and OSV) resulted from reduced metabolic cost. The composition of fatty acids in the copepods varied mainly with temperature. Two fatty acids varied with p CO 2 : 16:0 tended to decrease with higher p CO 2 and 18:3n−3 tended to increase with higher p CO 2 . These observations suggest that elevated p CO 2 /lower pH in future oceans may have a beneficial effect on C. finmarchicus .

PlantACT! – how to tackle the climate crisis - Heribert Hirt; Salim Al-Babili; Marilia Almeida-Trapp; Antoine Martin; Manuel Aranda; Dorothea Bartels; Malcolm Bennett; Ikram Blilou; Damian Boer; Alix Boulouis; Chris Bowler; Sophie Brunel-Muguet; et al. (Trends in Plant Science, 2023)

Traits of dominant plant species drive normalized difference vegetation index in grasslands globally - Thore Engel; Helge Bruelheide; Daniela Hoss; Francesco M. Sabatini; Jan Altman; Mohammed A. S. Arfin‐Khan; Erwin Bergmeier; Tomáš Černý; Milan Chytrý; Matteo Dainese; Jürgen Dengler; Jiri Dolezal; et al. (Global Ecology and Biogeography, 2023)
Aim Theoretical, experimental and observational studies have shown that biodiversity–ecosystem functioning (BEF) relationships are influenced by functional community structure through two mutually non‐exclusive mechanisms: (1) the dominance effect (which relates to the traits of the dominant species); and (2) the niche partitioning effect [which relates to functional diversity (FD)]. Although both mechanisms have been studied in plant communities and experiments at small spatial extents, it remains unclear whether evidence from small‐extent case studies translates into a generalizable macroecological pattern. Here, we evaluate dominance and niche partitioning effects simultaneously in grassland systems world‐wide. Location Two thousand nine hundred and forty‐one grassland plots globally. Time period 2000–2014. Major taxa studied Vascular plants. Methods We obtained plot‐based data on functional community structure from the global vegetation plot database “sPlot”, which combines species composition with plant trait data from the “TRY” database. We used data on the community‐weighted mean (CWM) and FD for 18 ecologically relevant plant traits. As an indicator of primary productivity, we extracted the satellite‐derived normalized difference vegetation index (NDVI) from MODIS. Using generalized additive models and deviation partitioning, we estimated the contributions of trait CWM and FD to the variation in annual maximum NDVI, while controlling for climatic variables and spatial structure. Results Grassland communities dominated by relatively tall species with acquisitive traits had higher NDVI values, suggesting the prevalence of dominance effects for BEF relationships. We found no support for niche partitioning for the functional traits analysed, because NDVI remained unaffected by FD. Most of the predictive power of traits was shared by climatic predictors and spatial coordinates. This highlights the importance of community assembly processes for BEF relationships in natural communities. Main conclusions Our analysis provides empirical evidence that plant functional community structure and global patterns in primary productivity are linked through the resource economics and size traits of the dominant species. This is an important test of the hypotheses underlying BEF relationships at the global scale.

Prevalence of neonicotinoid insecticides in paired private-well tap water and human urine samples in a region of intense agriculture overlying vulnerable aquifers in eastern Iowa - Darrin A. Thompson; Dana W. Kolpin; Michelle L. Hladik; Hans-Joachim Lehmler; Shannon M. Meppelink; Matthew C. Poch; John D. Vargo; Victor A. Soupene; Nafis Md Irfan; Morgan Robinson; Kurunthachalam Kannan; Laura E. Beane Freeman; et al. (Chemosphere, 2023)

Juxtaposition of intensive agriculture, vulnerable aquifers, and mixed chemical/microbial exposures in private-well tapwater in northeast Iowa - Paul M. Bradley; Dana W. Kolpin; Darrin A. Thompson; Kristin M. Romanok; Kelly L. Smalling; Sara E. Breitmeyer; Mary C. Cardon; David M. Cwiertny; Nicola Evans; R. William Field; Michael J. Focazio; Laura E. Beane Freeman; et al. (Science of The Total Environment, 2023)

Multiple‐brooding rockfishes ( Sebastes spp.) can utilize stored sperm from individual sires to fertilize consecutive broods - Neosha S Kashef; David M. Stafford; Susan M. Sogard; John C. Garza; John C. Field; Elizabeth A. Gilbert‐Horvath (Journal of Fish Biology, 2023)
Viviparous rockfishes ( Sebastes spp., family Scorpaenidae) mate and store sperm in the ovaries for several months prior to fertilization, as oocytes develop for the parturition season. Although multiple paternity has been documented in single‐brooding rockfishes, paternity in consecutive broods of multiple‐brooding species has not been studied. Analyses of multilocus microsatellite genotypes in both residual larvae left in the ovary from a previous parturition and upcoming fertilized broods in the same ovary demonstrated evidence of the same sires in consecutive broods in chilipepper ( Sebastes goodei ) and speckled ( Sebastes ovalis ) rockfishes. One S. goodei mother showed evidence of multiple paternity from the same two sires in both consecutive broods. The ability to retain sperm, even after a parturition event, for use in subsequent broods, confers an advantage to ensure fertilization and allows for extension of the parturition season. This life‐history strategy provides a bet‐hedging advantage in the California Current system, an environmentally dynamic ecosystem where larval survivorship and subsequent recruitment to adult populations can vary temporally by orders of magnitude.

Links to rare climates do not translate into distinct traits for island endemics - Vanessa Cutts; Dagmar M. Hanz; Martha Paola Barajas‐Barbosa; Franziska Schrodt; Manuel J. Steinbauer; Carl Beierkuhnlein; Pierre Denelle; José María Fernández‐Palacios; Pierre Gaüzère; Matthias Grenié; Severin D. H. Irl; Nathan Kraft; et al. (Ecology Letters, 2023)
Current models of island biogeography treat endemic and non‐endemic species as if they were functionally equivalent, focussing primarily on species richness. Thus, the functional composition of island biotas in relation to island biogeographical variables remains largely unknown. Using plant trait data (plant height, leaf area and flower length) for 895 native species in the Canary Islands, we related functional trait distinctiveness and climate rarity for endemic and non‐endemic species and island ages. Endemics showed a link to climatically rare conditions that is consistent with island geological change through time. However, functional trait distinctiveness did not differ between endemics and non‐endemics and remained constant with island age. Thus, there is no obvious link between trait distinctiveness and occupancy of rare climates, at least for the traits measured here, suggesting that treating endemic and non‐endemic species as functionally equivalent in island biogeography is not fundamentally wrong.

Applying genetic technologies to combat infectious diseases in aquaculture - Nicholas A. Robinson; Diego Robledo; Lene Sveen; Rose Ruiz Daniels; Aleksei Krasnov; Andrew Coates; Ye Hwa Jin; Luke T. Barrett; Marie Lillehammer; Anne H. Kettunen; Ben L. Phillips; Tim Dempster; et al. (Reviews in Aquaculture, 2023)
Disease and parasitism cause major welfare, environmental and economic concerns for global aquaculture. In this review, we examine the status and potential of technologies that exploit genetic variation in host resistance to tackle this problem. We argue that there is an urgent need to improve understanding of the genetic mechanisms involved, leading to the development of tools that can be applied to boost host resistance and reduce the disease burden. We draw on two pressing global disease problems as case studies—sea lice infestations in salmonids and white spot syndrome in shrimp. We review how the latest genetic technologies can be capitalised upon to determine the mechanisms underlying inter‐ and intra‐species variation in pathogen/parasite resistance, and how the derived knowledge could be applied to boost disease resistance using selective breeding, gene editing and/or with targeted feed treatments and vaccines. Gene editing brings novel opportunities, but also implementation and dissemination challenges, and necessitates new protocols to integrate the technology into aquaculture breeding programmes. There is also an ongoing need to minimise risks of disease agents evolving to overcome genetic improvements to host resistance, and insights from epidemiological and evolutionary models of pathogen infestation in wild and cultured host populations are explored. Ethical issues around the different approaches for achieving genetic resistance are discussed. Application of genetic technologies and approaches has potential to improve fundamental knowledge of mechanisms affecting genetic resistance and provide effective pathways for implementation that could lead to more resistant aquaculture stocks, transforming global aquaculture.

Ensuring planetary survival: the centrality of organic carbon in balancing the multifunctional nature of soils - Peter M. Kopittke; Asmeret Asefaw Berhe; Yolima Carrillo; Timothy R. Cavagnaro; Deli Chen; Qing-Lin Chen; Mercedes Román Dobarco; Feike A. Dijkstra; Damien J. Field; Michael J. Grundy; Ji-Zheng He; Frances C. Hoyle; et al. (Critical Reviews in Environmental Science and Technology, 2022)

Radiation Oncology Education Collaborative Study Group Annual Spring Symposium: Initial Impact and Feedback - David M. Rosenberg; Steve E. Braunstein; Emma C. Fields; Erin F. Gillespie; Jillian R. Gunther; Rachel B. Jimenez; Raphael L. Yechieli; Daniel W. Golden (Journal of Cancer Education, 2022)

Trends in breast and prostate cancer screening and diagnostic procedures during the COVID-19 pandemic in central Massachusetts - Mara M. Epstein; Devi Sundaresan; Meagan Fair; Hassan Fouayzi; Erica T. Warner; Lawrence D. Garber; Jerry H. Gurwitz; Terry S. Field (Cancer Causes & Control, 2022)

State of the California Current Ecosystem in 2021: Winter is coming? - Andrew R. Thompson; Eric P. Bjorkstedt; Steven J. Bograd; Jennifer L. Fisher; Elliott L. Hazen; Andrew Leising; Jarrod A. Santora; Erin V. Satterthwaite; William J. Sydeman; Michaela Alksne; Toby D. Auth; Simone Baumann-Pickering; et al. (Frontiers in Marine Science, 2022)
In late 2020, models predicted that a strong La Niña would take place for the first time since 2013, and we assessed whether physical and biological indicators in 2021 were similar to past La Niñas in the California Current Ecosystem (CCE). The Pacific Decadal Oscillation and Oceanic Niño Index indeed remained negative throughout 2021; the North Pacific Gyre Oscillation Index, however, remained strongly negative. The seventh largest marine heatwave on record was unexpectedly present from April to the end of 2021; however, similar to past La Niñas, this mass of warm water mostly remained seaward of the continental shelf. As expected from past La Niñas, upwelling and chlorophyll were mostly high and sea surface temperature was low throughout the CCE; however, values were close to average south of Point Conception. Similar to past La Niñas, abundances of lipid-rich, northern copepods off Oregon increased. In northern California, unlike past La Niñas, the body size of North Pacific krill ( Euphausia pacifica ) was close to average. Predictably, overall krill abundance was above average in far northern California but, unexpectedly, below average south of Cape Mendocino. Off Oregon, similar to past La Niñas, larval abundances of three of six coastal species rose, while five of six southern/offshore taxa decreased in 2021. Off California, as expected based on 2020, Northern Anchovy ( Engraulis mordax ) were very abundant, while Pacific Sardine ( Sardinops sagax ) were low. Similar to past La Niñas, market squid ( Doryteuthis opalescens ) and young of the year (YOY) Pacific Hake ( Merluccius pacificus ), YOY sanddabs ( Citharichthys spp.), and YOY rockfishes ( Sebastes spp.) increased. Southern mesopelagic (e.g., Panama lightfish Vinciguerria lucetia , Mexican lampfish Triphoturus mexicanus ) larvae decreased as expected but were still well above average, while northern mesopelagic (e.g., northern lampfish Stenobrachius leucopsarus ) larvae increased but were still below average. In line with predictions, most monitored bird species had above-average reproduction in Oregon and California. California sea lion ( Zalophus californianus ) pup count, growth, and weight were high given the abundant Anchovy forage. The CCE entered an enduring La Niña in 2021, and assessing the responses of various ecosystem components helped articulate aspects of the system that are well understood and those that need further study.

Transitioning Roles from Residency to Attending Physician in Radiation Oncology - Jenna M. Kahn; Deborah DiazGranados; Emma C. Fields (Journal of Cancer Education, 2022)

Copepod interaction with small‐scale, dissipative eddies in turbulence: Comparison among three marine species - Dorsa Elmi; Donald R. Webster; David M. Fields (Limnology and Oceanography, 2022)
A physical model of a Burgers vortex was created in the laboratory with characteristics corresponding to dissipative‐scale eddies that copepods are likely to encounter in turbulent flows. The swimming behavior of three marine copepod species is assessed as a function of vortex strength in and around the flow structure with the vortex axis aligned vertically or horizontally in the water. The studied species are Acartia tonsa , an estuarine copepod with a hop‐sink swimming style; Temora longicornis , a coastal copepod with a cruise swimming style; and Calanus finmarchicus , an open‐ocean copepod with a cruise‐sink swimming style. The results show that copepods change their swimming behavior with the intensity of the Burgers vortex and reveal species‐specific responses in nearly all kinematic parameters. A. tonsa and C. finmarchicus exhibited the strongest behavioral response to increasing vortex strength and T. longicornis exhibited the weakest response. A. tonsa and T. longicornis showed no response to changes in vortex orientation, whereas the behavior of C. finmarchicus revealed some vortex orientation dependence. One common behavior among the species is that the swimming trajectory shape becomes increasingly curved and spiral around the vortex core with increasing vortex strength, which provides a means of local aggregation and increased encounter rate with food and mates. The results are interpreted in relation to differences in swimming style and setal morphology among the species.

Climatic and biogeographical drivers of functional diversity in the flora of the Canary Islands - Dagmar M. Hanz; Vanessa Cutts; Martha Paola Barajas‐Barbosa; Adam C. Algar; Carl Beierkuhnlein; José‐María Fernández‐Palacios; Richard Field; Holger Kreft; Manuel J. Steinbauer; Patrick Weigelt; Severin D. H. Irl (Global Ecology and Biogeography, 2022)
Aim Functional traits can help us to elucidate biogeographical and ecological processes driving assemblage structure. We analysed the functional diversity of plant species of different evolutionary origins across an island archipelago, along environmental gradients and across geological age, to assess functional aspects of island biogeographical theory. Location Canary Islands, Spain. Major taxa studied Spermatophytes. Time period Present day. Methods We collected data for four traits (plant height, leaf length, flower length and fruit length) associated with resource acquisition, competitive ability, reproduction and dispersal ability of 893 endemic, non‐endemic native and alien plant species ( c . 43% of the Canary Island flora) from the literature. Linking these traits to species occurrences and composition across a 500 m × 500 m grid, we calculated functional diversity for endemic, non‐endemic native and alien assemblages using multidimensional functional hypervolumes and related the resulting patterns to climatic (humidity) and island biogeographical (geographical isolation, topographic complexity and geological age) gradients. Results Trait space of endemic and non‐endemic native species overlapped considerably, and alien species added novel trait combinations, expanding the overall functional space of the Canary Islands. We found that functional diversity of endemic plant assemblages was highest in geographically isolated and humid grid cells. Functional diversity of non‐endemic native assemblages was highest in less isolated and humid grid cells. In contrast, functional diversity of alien assemblages was highest in arid ecosystems. Topographic complexity and geological age had only a subordinate effect on functional diversity across floristic groups. Main conclusions We found that endemic and non‐endemic native island species possess similar traits, whereas alien species tend to expand functional space in ecosystems where they have been introduced. The spatial distribution of the functional diversity of floristic groups is very distinct across environmental gradients, indicating that species assemblages of different evolutionary origins thrive functionally in dissimilar habitats.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Estimated life-history traits and movements of the Caribbean reef shark (Carcharhinus perezi) in The Bahamas based on tag-recapture data - Brendan S. Talwar; Darcy Bradley; Christopher Berry; Mark E. Bond; Ian A. Bouyoucos; Annabelle M. L. Brooks; Candace Y. A. Fields; Austin J. Gallagher; Tristan L. Guttridge; Annie E. Guttridge; Neil Hammerschlag; Ian Hamilton; et al. (Marine Biology, 2022)

Correction to: Tree-ring cellulose δ18O records similar large-scale climate influences as precipitation δ18O in the Northwest Territories of Canada - Robert D. Field; Laia Andreu-Hayles; R. D. D’arrigo; R. Oelkers; B. H. Luckman; D. Morimoto; E. Boucher; F. Gennaretti; I. Hermoso; A. Lavergne; M. Levesque (Climate Dynamics, 2022)

Higher buccal mitochondrial DNA and mitochondrial common deletion number are associated with markers of neurodegeneration and inflammation in cerebrospinal fluid - Dipesh Solanky; Jerel A. Fields; Jennifer E. Iudicello; Ronald J. Ellis; Donald Franklin; David B. Clifford; Benjamin B. Gelman; Christina M. Marra; Susan Morgello; Leah H. Rubin; Igor Grant; Robert K. Heaton; et al. (Journal of NeuroVirology, 2022)

Corrigendum: State of the California Current 2019–2020: Back to the Future With Marine Heatwaves? - Edward D. Weber; Toby D. Auth; Simone Baumann-Pickering; Timothy R. Baumgartner; Eric P. Bjorkstedt; Steven J. Bograd; Brian J. Burke; José L. Cadena-Ramírez; Elizabeth A. Daly; Martin de la Cruz; Heidi Dewar; John C. Field; et al. (Frontiers in Marine Science, 2022)

Tree-ring cellulose δ18O records similar large-scale climate influences as precipitation δ18O in the Northwest Territories of Canada - Robert D. Field; Laia Andreu-Hayles; R. D. D’arrigo; R. Oelkers; B. H. Luckman; D. Morimoto; E. Boucher; F. Gennaretti; I. Hermoso; A. Lavergne; M. Levesque (Climate Dynamics, 2022)

Peripartum cardiomyopathy: a global effort to find the cause and cure for the rare and little understood disease - Amy Li; K. Campbell; S. Lal; Y. Ge; A. Keogh; P. S. Macdonald; P. Lau; John Lai; W. A. Linke; J. Van der Velden; A. Field; B. Martinac; et al. (Biophysical Reviews, 2022)
In this review, we present our current understanding of peripartum cardiomyopathy (PPCM) based on reports of the incidence, diagnosis and current treatment options. We summarise opinions on whether PPCM is triggered by vascular and/or hormonal causes and examine the influence of comorbidities such as preeclampsia. Two articles published in 2021 strongly support the hypothesis that PPCM may be a familial disease. Using large cohorts of PPCM patients, they summarised the available genomic DNA sequence data that are expressed in human cardiomyocytes. While PPCM is considered a disease predominately affecting the left ventricle, there are data to suggest that some cases also involve right ventricular failure. Finally, we conclude that there is sufficient evidence to warrant an RNAseq investigation and that this would be most informative if performed at the cardiomyocytes level rather than analysing genomic DNA from the peripheral circulation. Given the rarity of PPCM, the combined resources of international human heart tissue biobanks have assembled 30 ventricular tissue samples from PPCM patients, and we are actively seeking to enlarge this patient base by collaborating with human heart tissue banks and research laboratories who would like to join this endeavour.

sPlotOpen – An environmentally balanced, open‐access, global dataset of vegetation plots - Francesco Maria Sabatini; Jonathan Lenoir; Tarek Hattab; Elise Aimee Arnst; Milan Chytrý; Jürgen Dengler; Patrice De Ruffray; Stephan M. Hennekens; Ute Jandt; Florian Jansen; Borja Jiménez‐Alfaro; Jens Kattge; et al. (Global Ecology and Biogeography, 2021)
Motivation Assessing biodiversity status and trends in plant communities is critical for understanding, quantifying and predicting the effects of global change on ecosystems. Vegetation plots record the occurrence or abundance of all plant species co‐occurring within delimited local areas. This allows species absences to be inferred, information seldom provided by existing global plant datasets. Although many vegetation plots have been recorded, most are not available to the global research community. A recent initiative, called ‘sPlot’, compiled the first global vegetation plot database, and continues to grow and curate it. The sPlot database, however, is extremely unbalanced spatially and environmentally, and is not open‐access. Here, we address both these issues by (a) resampling the vegetation plots using several environmental variables as sampling strata and (b) securing permission from data holders of 105 local‐to‐regional datasets to openly release data. We thus present sPlotOpen, the largest open‐access dataset of vegetation plots ever released. sPlotOpen can be used to explore global diversity at the plant community level, as ground truth data in remote sensing applications, or as a baseline for biodiversity monitoring. Main types of variable contained Vegetation plots ( n = 95,104) recording cover or abundance of naturally co‐occurring vascular plant species within delimited areas. sPlotOpen contains three partially overlapping resampled datasets ( c . 50,000 plots each), to be used as replicates in global analyses. Besides geographical location, date, plot size, biome, elevation, slope, aspect, vegetation type, naturalness, coverage of various vegetation layers, and source dataset, plot‐level data also include community‐weighted means and variances of 18 plant functional traits from the TRY Plant Trait Database. Spatial location and grain Global, 0.01–40,000 m². Time period and grain 1888–2015, recording dates. Major taxa and level of measurement 42,677 vascular plant taxa, plot‐level records. Software format Three main matrices (.csv), relationally linked.

State of the California Current 2019–2020: Back to the Future With Marine Heatwaves? - Edward D. Weber; Toby D. Auth; Simone Baumann-Pickering; Timothy R. Baumgartner; Eric P. Bjorkstedt; Steven J. Bograd; Brian J. Burke; José L. Cadena-Ramírez; Elizabeth A. Daly; Martin de la Cruz; Heidi Dewar; John C. Field; et al. (Frontiers in Marine Science, 2021)
The California Current System (CCS) has experienced large fluctuations in environmental conditions in recent years that have dramatically affected the biological community. Here we synthesize remotely sensed, hydrographic, and biological survey data from throughout the CCS in 2019–2020 to evaluate how recent changes in environmental conditions have affected community dynamics at multiple trophic levels. A marine heatwave formed in the north Pacific in 2019 and reached the second greatest area ever recorded by the end of summer 2020. However, high atmospheric pressure in early 2020 drove relatively strong Ekman-driven coastal upwelling in the northern portion of the CCS and warm temperature anomalies remained far offshore. Upwelling and cooler temperatures in the northern CCS created relatively productive conditions in which the biomass of lipid-rich copepod species increased, adult krill size increased, and several seabird species experienced positive reproductive success. Despite these conditions, the composition of the fish community in the northern CCS remained a mixture of both warm- and cool-water-associated species. In the southern CCS, ocean temperatures remained above average for the seventh consecutive year. Abundances of juvenile fish species associated with productive conditions were relatively low, and the ichthyoplankton community was dominated by a mixture of oceanic warm-water and cosmopolitan species. Seabird species associated with warm water also occurred at greater densities than cool-water species in the southern CCS. The population of northern anchovy, which has been resurgent since 2017, continued to provide an important forage base for piscivorous fishes, offshore colonies of seabirds, and marine mammals throughout the CCS. Coastal upwelling in the north, and a longer-term trend in warming in the south, appeared to be controlling the community to a much greater extent than the marine heatwave itself.

Farm-Related Injuries and Fatalities Involving Children, Youth, and Young Workers during Manure Storage, Handling, and Transport - Mahmoud M Nour; Willam E Field; Ji-Qin Ni; Yuan-Hsin Cheng (Journal of Agromedicine, 2021)

Using fisher‐contributed secondary fins to fill critical shark‐fisheries data gaps - Jessica R. Quinlan; Shannon J. O'Leary; Andrew T. Fields; Martin Benavides; Emily Stumpf; Ramon Carcamo; Joel Cruz; Derrick Lewis; Beverly Wade; George Amato; Sergios‐Orestis Kolokotronis; Gina M. Clementi; et al. (Conservation Biology, 2021)
Developing‐world shark fisheries are typically not assessed or actively managed for sustainability; one fundamental obstacle is the lack of species and size‐composition catch data. We tested and implemented a new and potentially widely applicable approach for collecting these data: mandatory submission of low‐value secondary fins (anal fins) from landed sharks by fishers and use of the fins to reconstruct catch species and size. Visual and low‐cost genetic identification were used to determine species composition, and linear regression was applied to total length and anal fin base length for catch‐size reconstruction. We tested the feasibility of this approach in Belize, first in a local proof‐of‐concept study and then scaling it up to the national level for the 2017–2018 shark‐fishing season (1,786 fins analyzed). Sixteen species occurred in this fishery. The most common were the Caribbean reef ( Carcharhinus perezi ), blacktip ( C. limbatus ), sharpnose (Atlantic [ Rhizoprionodon terraenovae ] and Caribbean [ R. porosus ] considered as a group), and bonnethead ( Sphyrna cf. tiburo ). Sharpnose and bonnethead sharks were landed primarily above size at maturity, whereas Caribbean reef and blacktip sharks were primarily landed below size at maturity. Our approach proved effective in obtaining critical data for managing the shark fishery, and we suggest the tools developed as part of this program could be exported to other nations in this region and applied almost immediately if there were means to communicate with fishers and incentivize them to provide anal fins. Outside the tropical Western Atlantic, we recommend further investigation of the feasibility of sampling of secondary fins, including considerations of time, effort, and cost of species identification from these fins, what secondary fin type to use, and the means with which to communicate with fishers and incentivize participation. This program could be a model for collecting urgently needed data for developing‐world shark fisheries globally. Article impact statement : Shark fins collected from fishers yield data critical to shark fisheries management in developing nations.

The relationship between niche breadth and range size of beech ( Fagus ) species worldwide - Qiong Cai; Erik Welk; Chengjun Ji; Wenjing Fang; Francesco M. Sabatini; Jianxiao Zhu; Jiangling Zhu; Zhiyao Tang; Fabio Attorre; Juan A. Campos; Andraž Čarni; Milan Chytrý; et al. (Journal of Biogeography, 2021)
Aim This work explores whether the commonly observed positive range size–niche breadth relationship exists for Fagus , one of the most dominant and widespread broad‐leaved deciduous tree genera in temperate forests of the Northern Hemisphere. Additionally, we ask whether the 10 extant Fagus species’ niche breadths and climatic tolerances are under phylogenetic control. Location Northern Hemisphere temperate forests. Taxon Fagus L. Methods Combining the global vegetation database sPlot with Chinese vegetation data, we extracted 107,758 relevés containing Fagus species. We estimated biotic and climatic niche breadths per species using plot‐based co‐occurrence data and a resource‐based approach, respectively. We examined the relationships of these estimates with range size and tested for their phylogenetic signal, prior to which a Random Forest (RF) analysis was applied to test which climatic properties are most conserved across the Fagus species. Results Neither biotic niche breadth nor climatic niche breadth was correlated with range size, and the two niche breadths were incongruent as well. Notably, the widespread North American F. grandifolia had a distinctly smaller biotic niche breadth than the Chinese Fagus species ( F. engleriana , F. hayatae , F. longipetiolata and F. lucida ) with restricted distributions in isolated mountains. The RF analysis revealed that cold tolerance did not differ among the 10 species, and thus may represent an ancestral, fixed trait. In addition, neither biotic nor climatic niche breadths are under phylogenetic control. Main Conclusions We interpret the lack of a general positive range size–niche breadth relationship within the genus Fagus as a result of the widespread distribution, high among‐region variation in available niche space, landscape heterogeneity and Quaternary history. The results hold when estimating niche sizes either by fine‐scale co‐occurrence data or coarse‐scale climate data, suggesting a mechanistic link between factors operating across spatial scales. Besides, there was no evidence for diverging ecological specialization within the genus Fagus .

Split sex ratios and genetic relatedness in a primitively eusocial sweat bee - Tanya M Pennell; Jeremy Field (Behavioral Ecology and Sociobiology, 2021)
In eusocial Hymenoptera, queens and their helper offspring should favour different sex investment ratios. Queens should prefer a 1:1 investment ratio, as they are equally related to offspring of both sexes ( r = 0.5). In contrast, helpers should favour an investment ratio of 3:1 towards the production of female brood. This conflict arises because helpers are more closely related to full sisters ( r = 0.75) than brothers ( r = 0.25). However, helpers should invest relatively more in male brood if relatedness asymmetry within their colony is reduced. This can occur due to queen replacement after colony orphaning, multiple paternity and the presence of unrelated alien helpers. We analysed an unprecedentedly large number of colonies ( n = 109) from a UK population of Lasioglossum malachurum , an obligate eusocial sweat bee, to tease apart the effects of these factors on colony-level investment ratios. We found that multiple paternity, unrelated alien helpers and colony orphaning were all common. Queen-right colonies invested relatively more in females than did orphaned colonies, producing a split sex ratio. However, investment ratios did not change due to multiple paternity or the presence of alien helpers, reducing inclusive fitness pay-offs for helpers. Queen control may also have been important: helpers rarely laid male eggs, and investment in female brood was lower when queens were large relative to their helpers. Genetic relatedness between helpers and the brood that they rear was 0.43 in one year and 0.37 in another year, suggesting that ecological benefits, as well as relatedness benefits, are necessary for the maintenance of helping behaviour. Significance statement How helping behaviour is maintained in eusocial species is a key topic in evolutionary biology. Colony-level sex investment ratio changes in response to relatedness asymmetries can dramatically influence inclusive fitness benefits for helpers in eusocial Hymenoptera. The extent to which helpers in primitively eusocial colonies can respond adaptively to different sources of variation in relatedness asymmetry is unclear. Using data from 109 colonies of the sweat bee Lasioglossum malachurum , we found that queen loss, but not multiple paternity or the presence of alien helpers, was correlated with colony sex investment ratios. Moreover, we quantified average helper-brood genetic relatedness to test whether it is higher than that predicted under solitary reproduction ( r = 0.5). Values equal to and below r = 0.5 suggest that relatedness benefits alone cannot explain the maintenance of helping behaviour. Ecological benefits of group living and/or coercion must also contribute.

Evolutionary trade‐offs of insecticide resistance — The fitness costs associated with target‐site mutations in the nAChR of Drosophila melanogaster - Rafael A. Homem; Bliss Buttery; Ewan Richardson; Yao Tan; Linda M. Field; Martin S. Williamson; T. G. Emyr Davies (Molecular Ecology, 2020)
The evolution of resistance to drugs and pesticides poses a major threat to human health and food security. Neonicotinoids are highly effective insecticides used to control agricultural pests. They target the insect nicotinic acetylcholine receptor and mutations of the receptor that confer resistance have been slow to develop, with only one field‐evolved mutation being reported to date. This is an arginine‐to‐threonine substitution at position 81 of the nAChR_β1 subunit in neonicotinoid‐resistant aphids. To validate the role of R81T in neonicotinoid resistance and to test whether it may confer any significant fitness costs to insects, CRISPR/Cas9 was used to introduce an analogous mutation in the genome of Drosophila melanogaster . Flies carrying R81T showed an increased tolerance (resistance) to neonicotinoid insecticides, accompanied by a significant reduction in fitness. In comparison, flies carrying a deletion of the whole nAChR_α6 subunit, the target site of spinosyns, showed an increased tolerance to this class of insecticides but presented almost no fitness deficits.

Implementing Ecosystem-Based Management Principles in the Design of a Salmon Ocean Ecology Program - Brian K. Wells; David D. Huff; Brian J. Burke; Richard D. Brodeur; Jarrod A. Santora; John C. Field; Kate Richerson; Nathan J. Mantua; Kurt L. Fresh; Michelle M. McClure; William H. Satterthwaite; Forbes Darby; et al. (Frontiers in Marine Science, 2020)

Similar factors underlie tree abundance in forests in native and alien ranges - Masha T. van der Sande; Helge Bruelheide; Wayne Dawson; Jürgen Dengler; Franz Essl; Richard Field; Sylvia Haider; Mark van Kleunen; Holger Kreft; Joern Pagel; Jan Pergl; Oliver Purschke; et al. (Global Ecology and Biogeography, 2020)
Aim Alien plant species can cause severe ecological and economic problems, and therefore attract a lot of research interest in biogeography and related fields. To identify potential future invasive species, we need to better understand the mechanisms underlying the abundances of invasive tree species in their new ranges, and whether these mechanisms differ between their native and alien ranges. Here, we test two hypotheses: that greater relative abundance is promoted by (a) functional difference from locally co‐occurring trees, and (b) higher values than locally co‐occurring trees for traits linked to competitive ability. Location Global. Time period Recent. Major taxa studied Trees. Methods We combined three global plant databases: sPlot vegetation‐plot database, TRY plant trait database and Global Naturalized Alien Flora (GloNAF) database. We used a hierarchical Bayesian linear regression model to assess the factors associated with variation in local abundance, and how these relationships vary between native and alien ranges and depend on species’ traits. Results In both ranges, species reach highest abundance if they are functionally similar to co‐occurring species, yet are taller and have higher seed mass and wood density than co‐occurring species. Main conclusions Our results suggest that light limitation leads to strong environmental and biotic filtering, and that it is advantageous to be taller and have denser wood. The striking similarities in abundance between native and alien ranges imply that information from tree species’ native ranges can be used to predict in which habitats introduced species may become dominant.

Fire affects the taxonomic and functional composition of soil microbial communities, with cascading effects on grassland ecosystem functioning - Sihang Yang; Qiaoshu Zheng; Yunfeng Yang; Mengting Yuan; Xingyu Ma; Nona R. Chiariello; Kathryn M. Docherty; Christopher B. Field; Jessica L. M. Gutknecht; Bruce A. Hungate; Audrey Niboyet; Xavier Le Roux; et al. (Global Change Biology, 2020)
Fire is a crucial event regulating the structure and functioning of many ecosystems. Yet few studies have focused on how fire affects taxonomic and functional diversities of soil microbial communities, along with changes in plant communities and soil carbon (C) and nitrogen (N) dynamics. Here, we analyze these effects in a grassland ecosystem 9 months after an experimental fire at the Jasper Ridge Global Change Experiment site in California, USA. Fire altered soil microbial communities considerably, with community assembly process analysis showing that environmental selection pressure was higher in burned sites. However, a small subset of highly connected taxa was able to withstand the disturbance. In addition, fire decreased the relative abundances of most functional genes associated with C degradation and N cycling, implicating a slowdown of microbial processes linked to soil C and N dynamics. In contrast, fire stimulated above‐ and belowground plant growth, likely enhancing plant–microbe competition for soil inorganic N, which was reduced by a factor of about 2. To synthesize those findings, we performed structural equation modeling, which showed that plants but not microbial communities were responsible for significantly higher soil respiration rates in burned sites. Together, our results demonstrate that fire ‘reboots’ the grassland ecosystem by differentially regulating plant and soil microbial communities, leading to significant changes in soil C and N dynamics.

Marine Vertebrate Biodiversity and Distribution Within the Central California Current Using Environmental DNA (eDNA) Metabarcoding and Ecosystem Surveys - Collin J. Closek; Jarrod A. Santora; Hilary A. Starks; Isaac D. Schroeder; Elizabeth A. Andruszkiewicz; Keith M. Sakuma; Steven J. Bograd; Elliott L. Hazen; John C. Field; Alexandria B. Boehm (Frontiers in Marine Science, 2019)

Resistance is futile: RNA-sequencing reveals differing responses to bat fungal pathogen in Nearctic Myotis lucifugus and Palearctic Myotis myotis - Thomas M. Lilley; Jenni M. Prokkola; Anna S. Blomberg; Steve Paterson; Joseph S. Johnson; Gregory G. Turner; Tomáš Bartonička; Erik Bachorec; DeeAnn M. Reeder; Kenneth A. Field (Oecologia, 2019)
Resistance and tolerance allow organisms to cope with potentially life-threatening pathogens. Recently introduced pathogens initially induce resistance responses, but natural selection favors the development of tolerance, allowing for a commensal relationship to evolve. Mycosis by Pseudogymnoascus destructans , causing white-nose syndrome (WNS) in Nearctic hibernating bats, has resulted in population declines since 2006. The pathogen, which spread from Europe, has infected species of Palearctic Myotis for a longer period. We compared ecologically relevant responses to the fungal infection in the susceptible Nearctic M. lucifugus and less susceptible Palearctic M. myotis , to uncover factors contributing to survival differences in the two species. Samples were collected from euthermic bats during arousal from hibernation, a naturally occurring phenomenon, during which transcriptional responses are activated. We compared the whole-transcriptome responses in wild bats infected with P. destructans hibernating in their natural habitat. Our results show dramatically different local transcriptional responses to the pathogen between uninfected and infected samples from the two species. Whereas we found 1526 significantly upregulated or downregulated transcripts in infected M. lucifugus , only one transcript was downregulated in M. myotis . The upregulated response pathways in M. lucifugus include immune cell activation and migration, and inflammatory pathways, indicative of an unsuccessful attempt to resist the infection. In contrast, M. myotis appears to tolerate P. destructans infection by not activating a transcriptional response. These host-microbe interactions determine pathology, contributing to WNS susceptibility, or commensalism, promoting tolerance to fungal colonization during hibernation that favors survival. Graphic abstract

Crown-of-thorns starfish impede the recovery potential of coral reefs following bleaching - M. D. E. Haywood; D. P. Thomson; R. C. Babcock; R. D. Pillans; J. K. Keesing; M. Miller; W. A. Rochester; A. Donovan; R. D. Evans; G. Shedrawi; S. N. Field (Marine Biology, 2019)

Phytoplankton odor modifies the response of Euphausia superba to flow - M. J. Weissburg; J. Yen; D. M. Fields (Polar Biology, 2019)

Development of methodology to document and code farm-related injuries and fatalities involving manure storage, handling and transport - with summary of 2017 incidents - Mahmoud M. Nour; William E. Field; Ji-Qin Ni; Charlene Cheng (Journal of Agromedicine, 2019)

Delineation of the Genera Haemoproteus and Plasmodium Using RNA-Seq and Multi-gene Phylogenetics - Jasper Toscani Field; Josh Weinberg; Staffan Bensch; Nubia E. Matta; Gediminas Valkiūnas; Ravinder N. M. Sehgal (Journal of Molecular Evolution, 2018)

Microbial community changes during a toxic cyanobacterial bloom in an alkaline Hungarian lake - Tisza A. S. Bell; Emel Sen-Kilic; Tamás Felföldi; Gabor Vasas; Matthew W. Fields; Brent M. Peyton (Antonie van Leeuwenhoek, 2018)

Genetic modifiers of radon-induced lung cancer risk: a genome-wide interaction study in former uranium miners - Albert Rosenberger; Rayjean J. Hung; David C. Christiani; Neil E. Caporaso; Geoffrey Liu; Stig E. Bojesen; Loic Le Marchand; Ch. A. Haiman; Demetrios Albanes; Melinda C. Aldrich; Adonina Tardon; G. Fernández-Tardón; et al. (International Archives of Occupational and Environmental Health, 2018)

Spiroplasma dominates the microbiome of khapra beetle: comparison with a congener, effects of life stage and temperature - D. M. Wilches; R. A. Laird; P. G. Fields; P. Coghlin; K. D. Floate (Symbiosis, 2018)

Effect of torpor on host transcriptomic responses to a fungal pathogen in hibernating bats - Kenneth A. Field; Brent J. Sewall; Jenni M. Prokkola; Gregory G. Turner; Marianne F. Gagnon; Thomas M. Lilley; J. Paul White; Joseph S. Johnson; Christopher L. Hauer; DeeAnn M. Reeder (Molecular Ecology, 2018)
Hibernation, the use of prolonged torpor to depress metabolism, is employed by mammals to conserve resources during extended periods of extreme temperatures and/or resource limitation. Mammalian hibernators arouse to euthermy periodically during torpor for reasons that are not well understood, and these arousals may facilitate immune processes. To determine whether arousals enable host responses to pathogens, we used dual RNA ‐Seq and a paired sampling approach to examine gene expression in a hibernating bat, the little brown myotis ( Myotis lucifugus ). During torpor, transcript levels differed in only a few genes between uninfected wing tissue and adjacent tissue infected with Pseudogymnoascus destructans , the fungal pathogen that causes white‐nose syndrome. Within 70–80 min after emergence from torpor, large changes in gene expression were observed due to local infection, particularly in genes involved in pro‐inflammatory host responses to fungal pathogens, but also in many genes involved in immune responses and metabolism. These results support the hypothesis that torpor is a period of relative immune dormancy and arousals allow for local immune responses in infected tissues during hibernation. Host–pathogen interactions were also found to regulate gene expression in the pathogen differently depending on the torpor state of the host. Hibernating species must balance the benefits of energy and water conservation achieved during torpor with the costs of decreased immune competence. Interbout arousals allow hibernators to optimize these, and other, trade‐offs during prolonged hibernation by enabling host responses to pathogens within brief, periodic episodes of euthermy.

Cover Image - D M Fields; A B Skiftesvik; H I Browman (Journal of Fish Diseases, 2018)

Behavioural responses of infective‐stage copepodids of the salmon louse ( Lepeophtheirus salmonis, Copepoda:Caligidae ) to host‐related sensory cues - D M Fields; A B Skiftesvik; H I Browman (Journal of Fish Diseases, 2018)
The salmon louse ( Lepeophtheirus salmonis [Krøyer]) is an ectoparasitic copepod that causes disease in farmed Atlantic salmon ( Salmo salar ) and may play a role in the decline of some wild salmonid populations. Controlling lice infestations is a major cost for the salmon industry; this has stimulated the pursuit of alternative approaches to controlling them. One such approach involves determining, and then disrupting, the sensory cues used by the parasite to find its host. In this context, we examined the behavioural responses of lice copepodids to light flicker—simulating light reflecting from the sides of the salmon host and/or the shadows cast by fish passing overhead—and water‐soluble chemicals released from the skin of the salmon. From these observations, we estimate that visual cues such as those presented here would operate at relatively long range (metres to tens of metres). A diffuse host‐related olfactory cue stimulated swimming, however, it remains unclear whether olfactory cues provide directional information. The observations presented herein could be used to disrupt the link between the parasite and host fish, using a large number of traps deployed at a distance from a salmon farm, for example, thereby reducing sea lice infestation pressure.

The global overlap of bioenergy and carbon sequestration potential - P. A. Turner; K. J. Mach; D. B. Lobell; S. M. Benson; E. Baik; D. L. Sanchez; C. B. Field (Climatic Change, 2018)

Cadmium favors F-actin depolymerization in rat renal mesangial cells by site-specific, disulfide-based dimerization of the CAP1 protein - Ying Liu; Weiqun Xiao; Manasi Shinde; Jeffrey Field; Douglas M. Templeton (Archives of Toxicology, 2018)

Linking inter-individual variability to endocrine disruptors: insights for epigenetic inheritance - Sarah E. Latchney; Ashley M. Fields; Martha Susiarjo (Mammalian Genome, 2018)

Energy conserving thermoregulatory patterns and lower disease severity in a bat resistant to the impacts of white-nose syndrome - Marianne S. Moore; Kenneth A. Field; Melissa J. Behr; Gregory G. Turner; Morgan E. Furze; Daniel W. F. Stern; Paul R. Allegra; Sarah A. Bouboulis; Chelsey D. Musante; Megan E. Vodzak; Matthew E. Biron; Melissa B. Meierhofer; et al. (Journal of Comparative Physiology B, 2018)

Whole genome comparative analysis of four Georgian grape cultivars - V. Tabidze; I. Pipia; M. Gogniashvili; N. Kunelauri; L. Ujmajuridze; M. Pirtskhalava; B. Vishnepolsky; A. G. Hernandez; C. J. Fields; Tengiz Beridze (Molecular Genetics and Genomics, 2017)

Voltage-gated sodium channels as targets for pyrethroid insecticides - Linda M. Field; T. G. Emyr Davies; Andrias O. O’Reilly; Martin S. Williamson; B. A. Wallace (European Biophysics Journal, 2017)

miR-451 limits CD4+ T cell proliferative responses to infection in mice - Lesley M. Chapman; Sara K. Ture; David J. Field; Craig N. Morrell (Immunologic Research, 2017)

Genomic evidence for population‐specific responses to co‐evolving parasites in a New Zealand freshwater snail - Laura Bankers; Peter Fields; Kyle E. McElroy; Jeffrey L. Boore; John M. Logsdon; Maurine Neiman (Molecular Ecology, 2017)
Reciprocal co‐evolving interactions between hosts and parasites are a primary source of strong selection that can promote rapid and often population‐ or genotype‐specific evolutionary change. These host–parasite interactions are also a major source of disease. Despite their importance, very little is known about the genomic basis of co‐evolving host–parasite interactions in natural populations, especially in animals. Here, we use gene expression and sequence evolution approaches to take critical steps towards characterizing the genomic basis of interactions between the freshwater snail Potamopyrgus antipodarum and its co‐evolving sterilizing trematode parasite, Microphallus sp., a textbook example of natural coevolution. We found that Microphallus ‐infected P. antipodarum exhibit systematic downregulation of genes relative to uninfected P. antipodarum . The specific genes involved in parasite response differ markedly across lakes, consistent with a scenario where population‐level co‐evolution is leading to population‐specific host–parasite interactions and evolutionary trajectories. We also used an F ST ‐based approach to identify a set of loci that represent promising candidates for targets of parasite‐mediated selection across lakes as well as within each lake population. These results constitute the first genomic evidence for population‐specific responses to co‐evolving infection in the P. antipodarum‐Microphallus interaction and provide new insights into the genomic basis of co‐evolutionary interactions in nature.

Training in the Conduct of Population-Based Multi-Site and Multi-Disciplinary Studies: the Cancer Research Network’s Scholars Program - Diana S. M. Buist; Terry S. Field; Matthew P. Banegas; Heather A. Clancy; V. Paul Doria-Rose; Mara M. Epstein; Robert T. Greenlee; Sarah McDonald; Hazel B. Nichols; Pamala A. Pawloski; Lawrence H. Kushi (Journal of Cancer Education, 2017)

A comparison of protein extraction methods optimizing high protein yields from marine algae and cyanobacteria - Lacey M. Field; Wayne R. Fagerberg; Kayla K. Gatto; S. Anne Böttger (Journal of Applied Phycology, 2017)

High‐resolution tide projections reveal extinction threshold in response to sea‐level rise - Christopher R. Field; Trina S. Bayard; Carina Gjerdrum; Jason M. Hill; Susan Meiman; Chris S. Elphick (Global Change Biology, 2017)
Sea‐level rise will affect coastal species worldwide, but models that aim to predict these effects are typically based on simple measures of sea level that do not capture its inherent complexity, especially variation over timescales shorter than 1 year. Coastal species might be most affected, however, by floods that exceed a critical threshold. The frequency and duration of such floods may be more important to population dynamics than mean measures of sea level. In particular, the potential for changes in the frequency and duration of flooding events to result in nonlinear population responses or biological thresholds merits further research, but may require that models incorporate greater resolution in sea level than is typically used. We created population simulations for a threatened songbird, the saltmarsh sparrow ( Ammodramus caudacutus ), in a region where sea level is predictable with high accuracy and precision. We show that incorporating the timing of semidiurnal high tide events throughout the breeding season, including how this timing is affected by mean sea‐level rise, predicts a reproductive threshold that is likely to cause a rapid demographic shift. This shift is likely to threaten the persistence of saltmarsh sparrows beyond 2060 and could cause extinction as soon as 2035. Neither extinction date nor the population trajectory was sensitive to the emissions scenarios underlying sea‐level projections, as most of the population decline occurred before scenarios diverge. Our results suggest that the variation and complexity of climate‐driven variables could be important for understanding the potential responses of coastal species to sea‐level rise, especially for species that rely on coastal areas for reproduction.

Genome-wide meta-analyses of nonsyndromic orofacial clefts identify novel associations between FOXE1 and all orofacial clefts, and TP63 and cleft lip with or without cleft palate - Elizabeth J. Leslie; Jenna C. Carlson; John R. Shaffer; Azeez Butali; Carmen J. Buxó; Eduardo E. Castilla; Kaare Christensen; Fred W. B. Deleyiannis; L. Leigh Field; Jacqueline T. Hecht; Lina Moreno; Ieda M. Orioli; et al. (Human Genetics, 2017)

Seasonal fecundity is not related to geographic position across a species’ global range despite a central peak in abundance - Katharine J. Ruskin; Matthew A. Etterson; Thomas P. Hodgman; Alyssa C. Borowske; Jonathan B. Cohen; Chris S. Elphick; Christopher R. Field; Rebecca A. Kern; Erin King; Alison R. Kocek; Adrienne I. Kovach; Kathleen M. O’Brien; et al. (Oecologia, 2017)

Ecosystem effects of invertebrate fisheries - Tyler D Eddy; Heike K Lotze; Elizabeth A Fulton; Marta Coll; Cameron H Ainsworth; Júlio Neves de Araújo; Catherine M Bulman; Alida Bundy; Villy Christensen; John C Field; Neil A Gribble; Mejs Hasan; et al. (Fish and Fisheries, 2017)
Since the 1950s, invertebrate fisheries catches have rapidly expanded globally to more than 10 million tonnes annually, with twice as many target species, and are now significant contributors to global seafood provision, export, trade and local livelihoods. Invertebrates play important and diverse functional roles in marine ecosystems, yet the ecosystem effects of their exploitation are poorly understood. Using 12 ecosystem models distributed worldwide, we analysed the trade‐offs of various invertebrate fisheries and their ecosystem effects as well as ecological indicators. Although less recognized for their contributions to marine food webs, our results show that the magnitude of trophic impacts of invertebrates on other species of commercial and conservation interest is comparable with those of forage fish. Generally, cephalopods showed the strongest ecosystem effects and were characterized by a strong top‐down predatory role. Lobster, and to a lesser extent, crabs, shrimp and prawns, also showed strong ecosystem effects, but at lower trophic levels. Benthic invertebrates, including epifauna and infauna, also showed considerable ecosystem effects, but with strong bottom‐up characteristics. In contrast, urchins, bivalves, and gastropods showed generally lower ecosystem effects in our simulations. Invertebrates also strongly contributed to benthic–pelagic coupling, with exploitation of benthic invertebrates impacting pelagic fishes and vice versa. Finally, on average, invertebrates produced maximum sustainable yield at lower levels of depletion (~45%) than forage fish (~65%), highlighting the need for management targets that avoid negative consequences for target species and marine ecosystems as a whole.

Insecticide resistance mediated by an exon skipping event - Madeleine Berger; Alin Mirel Puinean; Emma Randall; Christoph T. Zimmer; Wellington M. Silva; Pablo Bielza; Linda M. Field; David Hughes; Ian Mellor; Keywan Hassani‐Pak; Herbert A. A. Siqueira; Martin S. Williamson; et al. (Molecular Ecology, 2016)
Many genes increase coding capacity by alternate exon usage. The gene encoding the insect nicotinic acetylcholine receptor ( nAChR ) α6 subunit, target of the bio‐insecticide spinosad, is one example of this and expands protein diversity via alternative splicing of mutually exclusive exons. Here, we show that spinosad resistance in the tomato leaf miner, Tuta absoluta is associated with aberrant regulation of splicing of Ta α 6 resulting in a novel form of insecticide resistance mediated by exon skipping. Sequencing of the α6 subunit cDNA from spinosad selected and unselected strains of T. absoluta revealed all Ta α 6 transcripts of the selected strain were devoid of exon 3, with comparison of genomic DNA and mRNA revealing this is a result of exon skipping. Exon skipping cosegregated with spinosad resistance in survival bioassays, and functional characterization of this alteration using modified human nAChR α7, a model of insect α6, demonstrated that exon 3 is essential for receptor function and hence spinosad sensitivity. DNA and RNA sequencing analyses suggested that exon skipping did not result from genetic alterations in intronic or exonic cis ‐regulatory elements, but rather was associated with a single epigenetic modification downstream of exon 3a, and quantitative changes in the expression of trans ‐acting proteins that have known roles in the regulation of alternative splicing. Our results demonstrate that the intrinsic capacity of the α6 gene to generate transcript diversity via alternative splicing can be readily exploited during the evolution of resistance and identifies exon skipping as a molecular alteration conferring insecticide resistance.

Topography‐driven isolation, speciation and a global increase of endemism with elevation - Manuel J. Steinbauer; Richard Field; John‐Arvid Grytnes; Panayiotis Trigas; Claudine Ah‐Peng; Fabio Attorre; H. John B. Birks; Paulo A. V. Borges; Pedro Cardoso; Chang‐Hung Chou; Michele De Sanctis; Miguel M. de Sequeira; et al. (Global Ecology and Biogeography, 2016)
Aim Higher‐elevation areas on islands and continental mountains tend to be separated by longer distances, predicting higher endemism at higher elevations; our study is the first to test the generality of the predicted pattern. We also compare it empirically with contrasting expectations from hypotheses invoking higher speciation with area, temperature and species richness. Location Thirty‐two insular and 18 continental elevational gradients from around the world. Methods We compiled entire floras with elevation‐specific occurrence information, and calculated the proportion of native species that are endemic (‘percent endemism’) in 100‐m bands, for each of the 50 elevational gradients. Using generalized linear models, we tested the relationships between percent endemism and elevation, isolation, temperature, area and species richness. Results Percent endemism consistently increased monotonically with elevation, globally. This was independent of richness–elevation relationships, which had varying shapes but decreased with elevation at high elevations. The endemism–elevation relationships were consistent with isolation‐related predictions, but inconsistent with hypotheses related to area, richness and temperature. Main conclusions Higher per‐species speciation rates caused by increasing isolation with elevation are the most plausible and parsimonious explanation for the globally consistent pattern of higher endemism at higher elevations that we identify. We suggest that topography‐driven isolation increases speciation rates in mountainous areas, across all elevations and increasingly towards the equator. If so, it represents a mechanism that may contribute to generating latitudinal diversity gradients in a way that is consistent with both present‐day and palaeontological evidence.

Brandt's cormorant diet (1994–2012) indicates the importance of fall ocean conditions for northern anchovy in central C alifornia - Meredith L. Elliott; Annie E. Schmidt; Sara Acosta; Russell Bradley; Pete Warzybok; Keith M. Sakuma; John C. Field; Jaime Jahncke (Fisheries Oceanography, 2016)
Effective ecosystem‐based management requires a comprehensive understanding of the functional links in the system. In many marine systems, forage species constitute a critical link between primary production and upper trophic level marine predators. As top predators, seabirds can be indicators of the forage species they consume and the ocean processes that influence these populations. We analyzed the diet and breeding success for the years 1994, 2003, 2005, and 2007–2012 of the Brandt's cormorant ( Phalacrocorax penicillatus ), a piscivorous diving seabird, breeding in central California, to evaluate the extent to which cormorant diet composition relates to prey availability, and how diet composition relates to breeding success and ocean conditions. Cormorant diet was primarily composed of young‐of‐the‐year ( YOY ) northern anchovy ( Engraulis mordax ), YOY rockfish ( Sebastes spp.), and several species of small flatfish (order Pleuronectiformes). YOY rockfish consumption was positively related to their abundance as measured in a late spring pelagic midwater trawl survey. Northern anchovy appeared to be the most important prey as its consumption was positively related to cormorant breeding success. More northern anchovy were consumed in years where warm‐water conditions prevailed in the fall season before cormorant breeding. Thus, warm ocean conditions in the fall appear to be an important contributing factor in producing a strong year‐class of northern anchovy in central California and consequently a strong‐year class of Brandt's cormorant on the Farallon Islands.

New directions in island biogeography - Ana M. C. Santos; Richard Field; Robert E. Ricklefs (Global Ecology and Biogeography, 2016)
Aim Much of our current understanding of ecological and evolutionary processes comes from island research. With the increasing availability of data on distributions and phylogenetic relationships and new analytical approaches to understanding the processes that shape species distributions and interactions, a re‐evaluation of this ever‐interesting topic is timely. Location Islands globally. Methods We start by arguing that the reasons why island research has achieved so much in the past also apply to the future. We then critically assess the current state of island biogeography, focusing on recent changes in emphasis, including research featured in this special issue of Global Ecology and Biogeography . Finally, we suggest promising themes for the future. We cover both ecological and evolutionary topics, although the greater emphasis on island ecology reflects our own backgrounds and interests. Results Much ecological theory has been directly or indirectly influenced by research on island biotas. Currently, island biogeography is renascent, with research focusing on, among other things, patterns and processes underlying species interaction networks, species coexistence and the assembly of island communities through ecological and evolutionary time. Continuing island research should provide additional insight into biological invasions and other impacts of human activities, functional diversity and ecosystem functioning, extinction and diversification, species pools and more. Deeper understanding of the similarities and differences between island and mainland systems will aid transferability of island theory to continental regions. Main conclusions As research in biogeography and related fields expands in new directions, islands continue to provide opportunities for developing insights, both as natural laboratories for ecology and evolution and because of the exceptions islands often present to the usual ‘rules’ of ecology. New data collection initiatives are needed on islands world‐wide and should be directed towards filling gaps in our knowledge of within‐island distributions of species, as well as the functional traits and phylogenetic relationships of island species.

Interdependence of DNA mismatch repair proteins MLH1 and MSH2 in apoptosis in human colorectal carcinoma cell lines - Samar Hassen; Akhtar A. Ali; Surya P. Kilaparty; Qudes A. Al-Anbaky; Waqar Majeed; Bruce M. Boman; Jeremy Z. Fields; Nawab Ali (Molecular and Cellular Biochemistry, 2016)

The effect of flavanol-rich cocoa on cerebral perfusion in healthy older adults during conscious resting state: a placebo controlled, crossover, acute trial - Daniel J. Lamport; Deepa Pal; Christina Moutsiana; David T. Field; Claire M. Williams; Jeremy P. E. Spencer; Laurie T. Butler (Psychopharmacology, 2015)

Variability in rockfish (Sebastes spp.) fecundity: species contrasts, maternal size effects, and spatial differences - Sabrina G. Beyer; Susan M. Sogard; Chris J. Harvey; John C. Field (Environmental Biology of Fishes, 2015)

Health Literacy and Pap Testing in Insured Women - K. M. Mazor; A. E. Williams; D. W. Roblin; B. Gaglio; S. L. Cutrona; M. E. Costanza; P. K. J. Han; J. L. Wagner; H. Fouayzi; T. S. Field (Journal of Cancer Education, 2014)

Defining and Evaluating the Umbrella Species Concept for Conserving and Restoring Landscape Connectivity - IAN BRECKHEIMER; NICK M. HADDAD; WILLIAM F. MORRIS; ANNE M. TRAINOR; WILLIAM R. FIELDS; R. TODD JOBE; BRIAN R. HUDGENS; AARON MOODY; JEFFREY R. WALTERS (Conservation Biology, 2014)
Conserving or restoring landscape connectivity between patches of breeding habitat is a common strategy to protect threatened species from habitat fragmentation. By managing connectivity for some species, usually charismatic vertebrates, it is often assumed that these species will serve as conservation umbrellas for other species. We tested this assumption by developing a quantitative method to measure overlap in dispersal habitat of 3 threatened species—a bird (the umbrella), a butterfly, and a frog—inhabiting the same fragmented landscape. Dispersal habitat was determined with Circuitscape, which was parameterized with movement data collected for each species. Despite differences in natural history and breeding habitat, we found substantial overlap in the spatial distributions of areas important for dispersal of this suite of taxa. However, the intuitive umbrella species (the bird) did not have the highest overlap with other species in terms of the areas that supported connectivity. Nevertheless, we contend that when there are no irreconcilable differences between the dispersal habitats of species that cohabitate on the landscape, managing for umbrella species can help conserve or restore connectivity simultaneously for multiple threatened species with different habitat requirements. Definición y Evaluación del Concepto de Especie Paraguas para Conservar y Restaurar la Conectividad de Paisajes

The miRNA23b-regulated signaling network as a key to cancer development—implications for translational research and therapeutics - Vignesh Viswanathan; Jeremy Fields; Bruce M. Boman (Journal of Molecular Medicine, 2014)

Nasal chondromesenchymal hamartomas arise secondary to germline and somatic mutations of DICER1 in the pleuropulmonary blastoma tumor predisposition disorder - Douglas R. Stewart; Yoav Messinger; Gretchen M. Williams; Jiandong Yang; Amanda Field; Kris Ann P. Schultz; Laura A. Harney; Leslie A. Doros; Louis P. Dehner; D. Ashley Hill (Human Genetics, 2014)

High pH (and not free ammonia) is responsible for Anammox inhibition in mildly alkaline solutions with excess of ammonium - D. Puyol; J. M. Carvajal-Arroyo; G. B. Li; A. Dougless; M. Fuentes-Velasco; R. Sierra-Alvarez; J. A. Field (Biotechnology Letters, 2014)

HOX genes and their role in the development of human cancers - Seema Bhatlekar; Jeremy Z. Fields; Bruce M. Boman (Journal of Molecular Medicine, 2014)

The Role of Nitrogen Deposition in Widespread Plant Community Change Across Semi-natural Habitats - Chris D. Field; Nancy B. Dise; Richard J. Payne; Andrea J. Britton; Bridget A. Emmett; Rachel C. Helliwell; Steve Hughes; Laurence Jones; Steven Lees; Jonathan R. Leake; Ian D. Leith; Gareth K. Phoenix; et al. (Ecosystems, 2014)

Heather Moorland Vegetation and Air Pollution: A Comparison and Synthesis of Three National Gradient Studies - Richard J. Payne; Simon J. M. Caporn; Christopher D. Field; Jacky A. Carroll; Jill L. Edmondson; Andrea Britton; Nancy B. Dise (Water, Air, & Soil Pollution, 2014)

The regeneration of highly bioavailable iron by meso‐ and microzooplankton - Jochen Nuester; Steve Shema; Alexander Vermont; David M. Fields; Benjamin S. Twining (Limnology and Oceanography, 2014)
The micronutrient iron (Fe) is rapidly cycled in surface waters, and regenerated Fe supports much of the phytoplankton growth in open ocean waters. Meso‐ and microzooplankton grazing are both important mechanisms to regenerate Fe, but the chemical conditions in the respective digestive systems are different and might affect the bioavailability of Fe. We conducted radiotracer grazing experiments with the copepod Acartia tonsa or the heterotrophic dinoflagellate Oxyrrhis marina feeding on the diatom Thalassiosira pseudonana or the coccolithophore Emiliania huxleyi . Uptake of regenerated 55 Fe by a separate T. pseudonana culture was compared to the uptake of inorganic Fe. Iron regenerated by A. tonsa was taken up 4‐ to 7‐fold faster than inorganic iron. In contrast, no difference was detected between the uptake rate of inorganic Fe and Fe regenerated by O. marina . Ingestion of different prey by A. tonsa revealed that Fe released during diatom digestion was taken up 1.8‐fold faster than Fe released from coccolithophore digestion. Digestive systems and the chemical makeup of the ingested prey are crucial in determining the bioavailability of regenerated Fe. Differences in pH and oxygen saturation between digestive vacuoles and guts may affect the speciation of regenerated Fe, and the release of ferrous Fe might contribute to the bioavailability of regenerated Fe. The ecological structure determines the importance of regenerated Fe for a particular ecosystem.

Aquatic invertebrate communities in tank bromeliads: how well do classic ecological patterns apply? - M. Jocque; R. Field (Hydrobiologia, 2014)

Ripping Improves Tree Survival and Growth on Unused Reclaimed Mined Lands - Christopher W. Fields-Johnson; James A. Burger; Daniel M. Evans; Carl E. Zipper (Environmental Management, 2014)

Analysis of surface binding sites (SBSs) in carbohydrate active enzymes with focus on glycoside hydrolase families 13 and 77 — a mini-review - Darrell Cockburn; Casper Wilkens; Christian Ruzanski; Susan Andersen; Jonas Willum Nielsen; Alison M. Smith; Robert A. Field; Martin Willemoës; Maher Abou Hachem; Birte Svensson (Biologia, 2014)

Identification and Expression Profile of Two Putative Odorant-Binding Proteins from the Neotropical Brown Stink Bug, Euschistus heros (Fabricius) (Hemiptera: Pentatomidae) - L R Farias; D P Paula; J J Zhou; R Liu; G J Pappas; M C B Moraes; R A Laumann; M Borges; M A Birkett; J A Pickett; L M Field; S N Báo (Neotropical Entomology, 2014)

Nitrite (not free nitrous acid) is the main inhibitor of the anammox process at common pH conditions - D. Puyol; J. M. Carvajal-Arroyo; R. Sierra-Alvarez; J. A. Field (Biotechnology Letters, 2014)

An end-to-end coupled model ROMS-N 2 P 2 Z 2 D 2 -OSMOSE of the southern Benguela foodweb: parameterisation, calibration and pattern-oriented validation - M Travers-Trolet; Y-J Shin; JG Field (African Journal of Marine Science, 2014)

Rapid fluctuations in flow and water-column properties in Asan Bay, Guam: implications for selective resilience of coral reefs in warming seas - C. D. Storlazzi; M. E. Field; O. M. Cheriton; M. K. Presto; J. B. Logan (Coral Reefs, 2013)

Sub-lethal exposure to ultraviolet radiation reduces prey consumption by Atlantic cod larvae (Gadus morhua) - Yuichi Fukunishi; Howard I. Browman; Caroline M. F. Durif; Reidun M. Bjelland; Steven D. Shema; David M. Fields; Anne Berit Skiftesvik (Marine Biology, 2013)

Alcohol dependent patients have weak negative rather than strong positive implicit alcohol associations - Joanne M. Dickson; Claire Gately; Matt Field (Psychopharmacology, 2013)

Hexavalent chromium reduction by Cellulomonas sp. strain ES6: the influence of carbon source, iron minerals, and electron shuttling compounds - Erin K. Field; Robin Gerlach; Sridhar Viamajala; Laura K. Jennings; Brent M. Peyton; William A. Apel (Biodegradation, 2013)

SedPods: a low-cost coral proxy for measuring net sedimentation - M. E. Field; H. Chezar; C. D. Storlazzi (Coral Reefs, 2013)

Varenicline decreases alcohol consumption in heavy-drinking smokers - Jennifer M. Mitchell; Candice H. Teague; Andrew S. Kayser; Selena E. Bartlett; Howard L. Fields (Psychopharmacology, 2012)

Use of sodium bicarbonate to stimulate triacylglycerol accumulation in the chlorophyte Scenedesmus sp. and the diatom Phaeodactylum tricornutum - Robert D. Gardner; Keith E. Cooksey; Florence Mus; Richard Macur; Karen Moll; Everett Eustance; Ross P. Carlson; Robin Gerlach; Matthew W. Fields; Brent M. Peyton (Journal of Applied Phycology, 2012)

Eruption of kimberlite magmas: physical volcanology, geomorphology and age of the youngest kimberlitic volcanoes known on earth (the Upper Pleistocene/Holocene Igwisi Hills volcanoes, Tanzania) - Richard J. Brown; S. Manya; I. Buisman; G. Fontana; M. Field; C. Mac Niocaill; R. S. J. Sparks; F. M. Stuart (Bulletin of Volcanology, 2012)

Microbial communities and their responses to simulated global change fluctuate greatly over multiple years - Jessica L. M. Gutknecht; Christopher B. Field; Teri C. Balser (Global Change Biology, 2012)
We used microbial lipid analysis to analyze microbial biomass and community structure during 6 years of experimental treatment at the J asper R idge G lobal C hange E xperiment ( JRGCE ), a long‐term multi‐factor global change experiment in a C alifornia annual grassland. The microbial community fingerprint and specific biomarkers varied substantially from year to year, in both control and experimental treatment plots. Possible drivers of the variability included plant growth, soil moisture, and ambient temperature. Surprisingly, background variation in the microbial community was of a larger magnitude than even very significant treatment effects, and this variation appeared to constrain responses to treatment. Microbial communities were mostly not responsive or not consistently responsive to the experimental treatments. Both arbuscular mycorrhizal fungi biomarker abundance (16 : 1 ω5c) and the fungal to bacterial ratio were lower under nitrogen addition in most years. Bacterial lipid biomarker abundances (15 : 0 iso and 16 : 1 ω7c) were higher under nitrogen addition in 2002, the year of largest microbial biomass, suggesting that bacteria could respond more to nitrogen addition in years of better growth conditions. Nitrogen addition and warming led to an interactive effect on the G ram‐positive bacterial biomarker and the fungal to bacterial ratio. These patterns indicate that in C alifornia grassland ecosystems, microbial communities may not respond substantially to future changes in climate and that nitrogen deposition may be a determinant of the soil response to global change. Further, year‐to‐year variation in microbial growth or community composition may be important determinants of ecosystem response to global change.

Trophic ecology of reef sharks determined using stable isotopes and telemetry - C. W. Speed; M. G. Meekan; I. C. Field; C. R. McMahon; K. Abrantes; C. J. A. Bradshaw (Coral Reefs, 2012)

Antioxidants can extend lifespan of Brachionus manjavacas (Rotifera), but only in a few combinations - Terry W. Snell; Allison M. Fields; Rachel K. Johnston (Biogerontology, 2012)

Evidence for reproductive philopatry in the bull shark Carcharhinus leucas - B. J. Tillett; M. G. Meekan; I. C. Field; D. C. Thorburn; J. R. Ovenden (Journal of Fish Biology, 2012)
Reproductive philopatry in bull sharks Carcharhinus leucas was investigated by comparing mitochondrial (NADH dehydrogenase subunit 4, 797 base pairs and control region genes 837 base pairs) and nuclear (three microsatellite loci) DNA of juveniles sampled from 13 river systems across northern Australia. High mitochondrial and low microsatellite genetic diversity among juveniles sampled from different rivers (mitochondrial φ ST = 0·0767, P F ST = −0·0022, P > 0·05) supported female reproductive philopatry. Genetic structure was not further influenced by geographic distance ( P > 0·05) or long‐shore barriers to movement ( P > 0·05). Additionally, results suggest that C. leucas in northern Australia has a long‐term effective population size of 11 000–13 000 females and has undergone population bottlenecks and expansions that coincide with the timing of the last ice‐ages.

Neutral metallated and meso-substituted porphyrins as antimicrobial agents against Gram-positive pathogens - W. N. Burda; K. B. Fields; J. B. Gill; R. Burt; M. Shepherd; X. P. Zhang; L. N. Shaw (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Pleistocene isolation, secondary introgression and restricted contemporary gene flow in the pig-eye shark, Carcharhinus amboinensis across northern Australia - B. J. Tillett; M. G. Meekan; D. Broderick; I. C. Field; G. Cliff; J. R. Ovenden (Conservation Genetics, 2012)

Evaluation and remediation of bulk soap dispensers for biofilm - Lindsey A. Lorenz; Bradley D. Ramsay; Darla M. Goeres; Matthew W. Fields; Carrie A. Zapka; David R. Macinga (Biofouling, 2012)

Fine-scale observations of the predatory behaviour of the carnivorous copepod Paraeuchaeta norvegica and the escape responses of their ichthyoplankton prey, Atlantic cod (Gadus morhua) - Howard I. Browman; Jeannette Yen; David M. Fields; Jean-François St-Pierre; Anne Berit Skiftesvik (Marine Biology, 2011)

Geology of the BK9 kimberlite (Damtshaa, Botswana): implications for the formation of dark volcaniclastic kimberlite - B. Buse; R. S. J. Sparks; M. Field; J. C. Schumacher; K. Chisi; T. Tlhaodi (Bulletin of Volcanology, 2011)

Influence of carbon sources and electron shuttles on ferric iron reduction by Cellulomonas sp. strain ES6 - Robin Gerlach; Erin K. Field; Sridhar Viamajala; Brent M. Peyton; William A. Apel; Al B. Cunningham (Biodegradation, 2011)

Numerical modeling of the impact of sea-level rise on fringing coral reef hydrodynamics and sediment transport - C. D. Storlazzi; E. Elias; M. E. Field; M. K. Presto (Coral Reefs, 2011)

Upper ocean stratification and sea ice growth rates during the summer-fall transition, as revealed by Elephant seal foraging in the Adélie Depression, East Antarctica - G. D. Williams; M. Hindell; M.-N. Houssais; T. Tamura; I. C. Field (Ocean Science, 2011)
Southern elephant seals (Mirounga leonina), fitted with Conductivity-Temperature-Depth sensors at Macquarie Island in January 2005 and 2010, collected unique oceanographic observations of the Adélie and George V Land continental shelf (140–148° E) during the summer-fall transition (late February through April). This is a key region of dense shelf water formation from enhanced sea ice growth/brine rejection in the local coastal polynyas. In 2005, two seals occupied the continental shelf break near the grounded icebergs at the northern end of the Mertz Glacier Tongue for several weeks from the end of February. One of the seals migrated west to the Dibble Ice Tongue, apparently utilising the Antarctic Slope Front current near the continental shelf break. In 2010, immediately after that year's calving of the Mertz Glacier Tongue, two seals migrated to the same region but penetrated much further southwest across the Adélie Depression and sampled the Commonwealth Bay polynya from March through April. Here we present observations of the regional oceanography during the summer-fall transition, in particular (i) the zonal distribution of modified Circumpolar Deep Water exchange across the shelf break, (ii) the upper ocean stratification across the Adélie Depression, including alongside iceberg C-28 that calved from the Mertz Glacier and (iii) the convective overturning of the deep remnant seasonal mixed layer in Commonwealth Bay from sea ice growth. Heat and freshwater budgets to 200–300 m are used to estimate the ocean heat content (400→50 MJ m−2), flux (50–200 W m−2 loss) and sea ice growth rates (maximum of 7.5–12.5 cm day−1). Mean seal-derived sea ice growth rates were within the range of satellite-derived estimates from 1992–2007 using ERA-Interim data. We speculate that the continuous foraging by the seals within Commonwealth Bay during the summer/fall transition was due to favorable feeding conditions resulting from the convective overturning of the deep seasonal mixed layer and chlorophyll maximum that is a reported feature of this location.

The use (and misuse) of sediment traps in coral reef environments: theory, observations, and suggested protocols - C. D. Storlazzi; M. E. Field; M. H. Bothner (Coral Reefs, 2011)

Quantifying movement patterns for shark conservation at remote coral atolls in the Indian Ocean - I. C. Field; M. G. Meekan; C. W. Speed; W. White; C. J. A. Bradshaw (Coral Reefs, 2011)

Coordinated approaches to quantify long‐term ecosystem dynamics in response to global change - YIQI LUO; JERRY MELILLO; SHULI NIU; CLAUS BEIER; JAMES S. CLARK; AIMÉE T. CLASSEN; ERIC DAVIDSON; JEFFREY S. DUKES; R. DAVE EVANS; CHRISTOPHER B. FIELD; CLAUDIA I. CZIMCZIK; MICHAEL KELLER; et al. (Global Change Biology, 2011)
Many serious ecosystem consequences of climate change will take decades or even centuries to emerge. Long‐term ecological responses to global change are strongly regulated by slow processes, such as changes in species composition, carbon dynamics in soil and by long‐lived plants, and accumulation of nutrient capitals. Understanding and predicting these processes require experiments on decadal time scales. But decadal experiments by themselves may not be adequate because many of the slow processes have characteristic time scales much longer than experiments can be maintained. This article promotes a coordinated approach that combines long‐term, large‐scale global change experiments with process studies and modeling. Long‐term global change manipulative experiments, especially in high‐priority ecosystems such as tropical forests and high‐latitude regions, are essential to maximize information gain concerning future states of the earth system. The long‐term experiments should be conducted in tandem with complementary process studies, such as those using model ecosystems, species replacements, laboratory incubations, isotope tracers, and greenhouse facilities. Models are essential to assimilate data from long‐term experiments and process studies together with information from long‐term observations, surveys, and space‐for‐time studies along environmental and biological gradients. Future research programs with coordinated long‐term experiments, process studies, and modeling have the potential to be the most effective strategy to gain the best information on long‐term ecosystem dynamics in response to global change.

Can crop albedo be increased through the modification of leaf trichomes, and could this cool regional climate? - Christopher E. Doughty; Christopher B. Field; Andrew M. S. McMillan (Climatic Change, 2011)

Binding of the General Odorant Binding Protein of Bombyx mori BmorGOBP2 to the Moth Sex Pheromone Components - Xiaoli He; George Tzotzos; Christine Woodcock; John A. Pickett; Tony Hooper; Linda M. Field; Jing-Jiang Zhou (Journal of Chemical Ecology, 2010)

Functional characterization of two chimeric proteins between a Petunia inflata S-locus F-box protein, PiSLF2, and a PiSLF-like protein, PiSLFLb-S2 - Allison M. Fields; Ning Wang; Zhihua Hua; Xiaoying Meng; Teh-hui Kao (Plant Molecular Biology, 2010)

Hydrogen peroxide‐induced oxidative stress responses in Desulfovibrio vulgaris Hildenborough - Aifen Zhou; Zhili He; Alyssa M. Redding‐Johanson; Aindrila Mukhopadhyay; Christopher L. Hemme; Marcin P. Joachimiak; Feng Luo; Ye Deng; Kelly S. Bender; Qiang He; Jay D. Keasling; David A. Stahl; et al. (Environmental Microbiology, 2010)
Summary To understand how sulphate‐reducing bacteria respond to oxidative stresses, the responses of Desulfovibrio vulgaris Hildenborough to H 2 O 2 ‐induced stresses were investigated with transcriptomic, proteomic and genetic approaches. H 2 O 2 and induced chemical species (e.g. polysulfide, ROS) and redox potential shift increased the expressions of the genes involved in detoxification, thioredoxin‐dependent reduction system, protein and DNA repair, and decreased those involved in sulfate reduction, lactate oxidation and protein synthesis. A gene coexpression network analysis revealed complicated network interactions among differentially expressed genes, and suggested possible importance of several hypothetical genes in H 2 O 2 stress. Also, most of the genes in PerR and Fur regulons were highly induced, and the abundance of a Fur regulon protein increased. Mutant analysis suggested that PerR and Fur are functionally overlapped in response to stresses induced by H 2 O 2 and reaction products, and the upregulation of thioredoxin‐dependent reduction genes was independent of PerR or Fur. It appears that induction of those stress response genes could contribute to the increased resistance of deletion mutants to H 2 O 2 ‐induced stresses. In addition, a conceptual cellular model of D. vulgaris responses to H 2 O 2 stress was constructed to illustrate that this bacterium may employ a complicated molecular mechanism to defend against the H 2 O 2 ‐induced stresses.

How effective are non-destructive sampling methods to assess aquatic invertebrate diversity in bromeliads? - M. Jocque; A. Kernahan; A. Nobes; C. Willians; R. Field (Hydrobiologia, 2010)

Effects of alcohol preload on attentional bias towards cocaine-related cues - Catharine Montgomery; Matt Field; Amanda M. Atkinson; Jon C. Cole; Andrew J. Goudie; Harry R. Sumnall (Psychopharmacology, 2010)

Calmodulin-binding transcription activator 1 mediates auxin signaling and responds to stresses in Arabidopsis - Yael Galon; Roni Aloni; Dikla Nachmias; Orli Snir; Ester Feldmesser; Sarah Scrase-Field; Joy M. Boyce; Nicolas Bouché; Marc R. Knight; Hillel Fromm (Planta, 2010)

The three-dimensional prey field of the northern krill, Meganyctiphanes norvegica, and the escape responses of their copepod prey - Mari B. Abrahamsen; Howard I. Browman; David M. Fields; Anne Berit Skiftesvik (Marine Biology, 2010)

Orientation affects the sensitivity of Acartia tonsa to fluid mechanical signals - David M. Fields (Marine Biology, 2010)

Fed-batch operation of an industrial cell culture process in shaken microwells - N. J. Silk; S. Denby; G. Lewis; M. Kuiper; D. Hatton; R. Field; F. Baganz; Gary J. Lye (Biotechnology Letters, 2010)

Anaerobic degradation of citrate under sulfate reducing and methanogenic conditions - Victor M. Gámez; Reyes Sierra-Alvarez; Rebecca J. Waltz; James A. Field (Biodegradation, 2009)

Occurrence and characterization of Salmonella enterica subspecies enterica serovar 9,12:l,v:- strains from Bulgaria, Denmark, and the United States - P. Petrov; R. S. Hendriksen; T. Kantardjiev; G. Asseva; G. Sørensen; P. Fields; M. Mikoleit; J. Whichard; J. R. McQuiston; M. Torpdahl; F. M. Aarestrup; F. J. Angulo (European Journal of Clinical Microbiology & Infectious Diseases, 2009)

Distribution of Anthocyanins Delivered from a Bioadhesive Black Raspberry Gel Following Topical Intraoral Application in Normal Healthy Volunteers - Carlos M. Ugalde; Zhongfa Liu; Chen Ren; Kenneth K. Chan; Kapila A. Rodrigo; Yhonghua Ling; Peter E. Larsen; Guillermo E. Chacon; Gary D. Stoner; Russell J. Mumper; Henry W. Fields; Susan R. Mallery (Pharmaceutical Research, 2009)

Geology of a complex kimberlite pipe (K2 pipe, Venetia Mine, South Africa): insights into conduit processes during explosive ultrabasic eruptions - R. J. Brown; M. Tait; M. Field; R. S. J. Sparks (Bulletin of Volcanology, 2009)

Spatial species‐richness gradients across scales: a meta‐analysis - Richard Field; Bradford A. Hawkins; Howard V. Cornell; David J. Currie; J. Alexandre F. Diniz‐Filho; Jean‐François Guégan; Dawn M. Kaufman; Jeremy T. Kerr; Gary G. Mittelbach; Thierry Oberdorff; Eileen M. O’Brien; John R. G. Turner (Journal of Biogeography, 2009)
Aim We surveyed the empirical literature to determine how well six diversity hypotheses account for spatial patterns in species richness across varying scales of grain and extent. Location Worldwide. Methods We identified 393 analyses (‘cases’) in 297 publications meeting our criteria. These criteria included the requirement that more than one diversity hypothesis was tested for its relationship with species richness. We grouped variables representing the hypotheses into the following ‘correlate types’: climate/productivity, environmental heterogeneity, edaphics/nutrients, area, biotic interactions and dispersal/history (colonization limitation or other historical or evolutionary effect). For each case we determined the ‘primary’ variable: the one most strongly correlated with taxon richness. We defined ‘primacy’ as the proportion of cases in which each correlate type was represented by the primary variable, relative to the number of times it was studied. We tested for differences in both primacy and mean coefficient of determination of the primary variable between the hypotheses and between categories of five grouping variables: grain, extent, taxon (animal vs. plant), habitat medium (land vs. water) and insularity (insular vs. connected). Results Climate/productivity had the highest overall primacy, and environmental heterogeneity and dispersal/history had the lowest. Primacy of climate/productivity was much higher in large‐grain and large‐extent studies than at smaller scales. It was also higher on land than in water, and much higher in connected systems than in insular ones. For other hypotheses, differences were less pronounced. Throughout, studies on plants and animals showed similar patterns. Coefficients of determination of the primary variables differed little between hypotheses and across the grouping variables, the strongest effects being low means in the smallest grain class and for edaphics/nutrients variables, and a higher mean for water than for land in connected systems but vice versa in insular systems. We highlight areas of data deficiency. Main conclusions Our results support the notion that climate and productivity play an important role in determining species richness at large scales, particularly for non‐insular, terrestrial habitats. At smaller extents and grain sizes, the primacy of the different types of correlates appears to differ little from null expectation. In our analysis, dispersal/history is rarely the best correlate of species richness, but this may reflect the difficulty of incorporating historical factors into regression models, and the collinearity between past and current climates. Our findings are consistent with the view that climate determines the capacity for species richness. However, its influence is less evident at smaller spatial scales, probably because (1) studies small in extent tend to sample little climatic range, and (2) at large grains some other influences on richness tend to vary mainly within the sampling unit.

Demise of reef-flat carbonate accumulation with late Holocene sea-level fall: evidence from Molokai, Hawaii - M. S. Engels; C. H. Fletcher; M. Field; C. L. Conger; C. Bochicchio (Coral Reefs, 2008)

Guarding against oversimplifying the fundamental drivers of southern elephant seal population dynamics - C. R. McMahon; I. C. Field; M. A. Hindell; S. C. De Little; C. J. A. Bradshaw (Journal of Biogeography, 2008)

Substrate specificity and molecular modelling of the feline herpesvirus-1 thymidine kinase - Islam T. M. Hussein; Ricardo Núñez Miguel; Laurence S. Tiley; Hugh J. Field (Archives of Virology, 2008)

Specificity of Phenolic Glycoside Induction in Willow Seedlings (Salix sericea) in Response to Herbivory - Mark J. Fields; Colin M. Orians (Journal of Chemical Ecology, 2006)

Interactive Effects of Fire, Elevated Carbon Dioxide, Nitrogen Deposition, and precipitation on a California Annual Grassland - Hugh A. L. Henry; Nona R. Chiariello; Peter M. Vitousek; Harold A. Mooney; Christopher B. Field (Ecosystems, 2006)

Interpreting tracer breakthrough tailing in a conduit-dominated karstic aquifer - N. Massei; H. Q. Wang; M. S. Field; J. P. Dupont; J. Rodet (Hydrogeology Journal, 2006)

Interpreting tracer breakthrough tailing in a conduit-dominated karstic aquifer - N. Massei; H. Q. Wang; M. S. Field; J. P. Dupont; M. Bakalowicz; J. Rodet (Hydrogeology Journal, 2006)

EST database for early flower development in California poppy (Eschscholzia californica Cham., Papaveraceae) tags over 6000 genes from a basal eudicot - John E. Carlson; James H. Leebens-Mack; P. Kerr Wall; Laura M. Zahn; Lukas A. Mueller; Lena L. Landherr; Yi Hu; Daniel C. Ilut; Jennifer M. Arrington; Stephanie Choirean; Annette Becker; Dawn Field; et al. (Plant Molecular Biology, 2006)

The application of acoustic Doppler current profilers to measure the timing and patterns of coral larval dispersal - C. D. Storlazzi; E. K. Brown; M. E. Field (Coral Reefs, 2006)

Comparative field performance over 3 years and two sites of transgenic wheat lines expressing HMW subunit transgenes - Peter R. Shewry; Stephen Powers; J. Michael Field; Roger J. Fido; Huw D. Jones; Gillian M. Arnold; Jevon West; Paul A. Lazzeri; Pilar Barcelo; Francisco Barro; Arthur S. Tatham; Frank Bekes; et al. (Theoretical and Applied Genetics, 2006)

Pleistocene fluvial sediments, palaeontology and archaeology of the upper River Thames at Latton, Wiltshire, England - S. G. Lewis; D. Maddy; C. Buckingham; G. R. Coope; M. H. Field; D. H. Keen; A. W. G. Pike; D. A. Roe; R. G. Scaife; K. Scott (Journal of Quaternary Science, 2006)
Pleistocene fluvial sediments of the Northmoor Member of the Upper Thames Formation exposed at Latton, Wiltshire, record episodic deposition close to the Churn–Thames confluence possibly spanning the interval from Marine Isotope Stages (MIS) 7 to 2. The sequence is dominated by gravel facies, indicating deposition by a high‐energy, gravel‐bed river. A number of fine‐grained organic sediment bodies within the sequence have yielded palaeoenvironmental and biostratigraphical data from Mollusca, Coleoptera, vertebrates, pollen and plant macrofossils. The basal deposit (Facies Association A) contains faunal material indicating temperate conditions. Most of the palaeontological evidence including a distinctive small form of mammoth ( Mammuthus cf. trogontherii ), together with the U‐series age estimate of >147.4 ± 20 kyr suggest correlation with MIS 7. The overlying deposits (Facies Associations B and C) represent deposition under a range of climatic conditions. Two fine‐grained organic deposits occurred within Association B; one (Association Ba) in the northern part of the pit as a channel fill and the other (Association Bb) in its southern part as a scour‐fill deposit. The coleopteran assemblages from Ba, indicate that it accumulated under temperate oceanic conditions, while Bb, which also yielded a radiocarbon age estimate of 39 560 ± 780 14 C yr BP, was formed under much colder and more continental climatic conditions. The sequence is considered to represent deposition within an alluvial fan formed at the Churn–Thames confluence; a depositional scenario which may account for the juxtaposition of sediments and fossils of widely differing age within the same altitudinal range. Copyright © 2006 John Wiley & Sons, Ltd.

Fate and biodegradability of sulfonated aromatic amines - Nico C. G. Tan; Annemarie van Leeuwen; Ellen M. van Voorthuizen; Peter Slenders; Francesc X. Prenafeta-Bold; Hardy Temmink; Gatze Lettinga; Jim A. Field (Biodegradation, 2005)

A single injection of the kappa opioid antagonist norbinaltorphimine increases ethanol consumption in rats - Jennifer M. Mitchell; Marisa T. Liang; Howard L. Fields (Psychopharmacology, 2005)

A single injection of the kappa opioid antagonist norbinaltorphimine increases ethanol consumption in rats - Jennifer M. Mitchell; Marisa T. Liang; Howard L. Fields (Psychopharmacology, 2005)

Zero tolerance ecology: improving ecological inference by modelling the source of zero observations - Tara G. Martin; Brendan A. Wintle; Jonathan R. Rhodes; Petra M. Kuhnert; Scott A. Field; Samantha J. Low‐Choy; Andrew J. Tyre; Hugh P. Possingham (Ecology Letters, 2005)
A common feature of ecological data sets is their tendency to contain many zero values. Statistical inference based on such data are likely to be inefficient or wrong unless careful thought is given to how these zeros arose and how best to model them. In this paper, we propose a framework for understanding how zero‐inflated data sets originate and deciding how best to model them. We define and classify the different kinds of zeros that occur in ecological data and describe how they arise: either from ‘true zero’ or ‘false zero’ observations. After reviewing recent developments in modelling zero‐inflated data sets, we use practical examples to demonstrate how failing to account for the source of zero inflation can reduce our ability to detect relationships in ecological data and at worst lead to incorrect inference. The adoption of methods that explicitly model the sources of zero observations will sharpen insights and improve the robustness of ecological analyses.

Effect of oxygen limitation on the in vitro antimicrobial susceptibility of clinical isolates of Pseudomonas aeruginosa grown planktonically and as biofilms - T. R. Field; A. White; J. S. Elborn; M. M. Tunney (European Journal of Clinical Microbiology & Infectious Diseases, 2005)

Interactive effects of elevated CO 2 , N deposition and climate change on extracellular enzyme activity and soil density fractionation in a California annual grassland - Hugh A. L. Henry; John D. Juarez; Christopher B. Field; Peter M. Vitousek (Global Change Biology, 2005)
Elevated CO 2 , N deposition and climate change can alter ecosystem‐level nutrient cycling both directly and indirectly. We explored the interactive effects of these environmental changes on extracellular enzyme activity and organic matter fractionation in soils of a California annual grassland. The activities of hydrolases (polysaccharide‐degrading enzymes and phosphatase) increased significantly in response to nitrate addition, which coincided with an increase in soluble C concentrations under ambient CO 2 . Water addition and elevated CO 2 had negative but nonadditive effects on the activities of these enzymes. In contrast, water addition resulted in an increase in the activities of lignin‐degrading enzymes (phenol oxidase and peroxidase), and a decrease in the free light fraction (FLF) of soil organic matter. Independent of treatment effects, lignin content in the FLF was negatively correlated with the quantity of FLF across all samples. Lignin concentrations were lower in the aggregate‐occluded light fraction (OLF) than the FLF, and there was no correlation between percent lignin and OLF quantity, which was consistent with the protection of soil organic matter in aggregates. Elevated CO 2 decreased the quantity of OLF and increased the OLF lignin concentration, however, which is consistent with increased degradation resulting from increased turnover of soil aggregates. Overall, these results suggest that the effects of N addition on hydrolase activity are offset by the interactive effects of water addition and elevated CO 2 , whereas water and elevated CO 2 may cause an increase in the breakdown of soil organic matter as a result of their effects on lignin‐degrading enzymes and soil aggregation, respectively.

A model for wave control on coral breakage and species distribution in the Hawaiian Islands - C. D. Storlazzi; E. K. Brown; M. E. Field; K. Rodgers; P. L. Jokiel (Coral Reefs, 2005)

Interactive effects of elevated CO2, N deposition and climate change on plant litter quality in a California annual grassland - Hugh A. L. Henry; Elsa E. Cleland; Christopher B. Field; Peter M. Vitousek (Oecologia, 2005)

Predictions and tests of climate‐based hypotheses of broad‐scale variation in taxonomic richness - David J. Currie; Gary G. Mittelbach; Howard V. Cornell; Richard Field; Jean‐Francois Guégan; Bradford A. Hawkins; Dawn M. Kaufman; Jeremy T. Kerr; Thierry Oberdorff; Eileen O'Brien; J. R. G. Turner (Ecology Letters, 2004)
Broad‐scale variation in taxonomic richness is strongly correlated with climate. Many mechanisms have been hypothesized to explain these patterns; however, testable predictions that would distinguish among them have rarely been derived. Here, we examine several prominent hypotheses for climate–richness relationships, deriving and testing predictions based on their hypothesized mechanisms. The ‘energy–richness hypothesis’ (also called the ‘more individuals hypothesis’) postulates that more productive areas have more individuals and therefore more species. More productive areas do often have more species, but extant data are not consistent with the expected causal relationship from energy to numbers of individuals to numbers of species. We reject the energy–richness hypothesis in its standard form and consider some proposed modifications. The ‘physiological tolerance hypothesis’ postulates that richness varies according to the tolerances of individual species for different sets of climatic conditions. This hypothesis predicts that more combinations of physiological parameters can survive under warm and wet than cold or dry conditions. Data are qualitatively consistent with this prediction, but are inconsistent with the prediction that species should fill climatically suitable areas. Finally, the ‘speciation rate hypothesis’ postulates that speciation rates should vary with climate, due either to faster evolutionary rates or stronger biotic interactions increasing the opportunity for evolutionary diversification in some regions. The biotic interactions mechanism also has the potential to amplify shallower, underlying gradients in richness. Tests of speciation rate hypotheses are few (to date), and their results are mixed.

Accuracy, efficiency and robustness of four algorithms allowing full sibship reconstruction from DNA marker data - K. Butler; C. Field; C. M. Herbinger; B. R. Smith (Molecular Ecology, 2004)
In the problem of reconstructing full sib pedigrees from DNA marker data, three existing algorithms and one new algorithm are compared in terms of accuracy, efficiency and robustness using real and simulated data sets. An algorithm based on the exclusion principle and another based on a maximization of the Simpson index were very accurate at reconstructing data sets comprising a few large families but had problems with data sets with limited family structure, while a Markov Chain Monte Carlo (MCMC) algorithm based on the maximization of a partition score had the opposite behaviour. An MCMC algorithm based on maximizing the full joint likelihood performed best in small data sets comprising several medium‐sized families but did not work well under most other conditions. It appears that the likelihood surface may be rough and presents challenges for the MCMC algorithm to find the global maximum. This likelihood algorithm also exhibited problems in reconstructing large family groups, due possibly to limits in computational precision. The accuracy of each algorithm improved with an increasing amount of information in the data set, and was very high with eight loci with eight alleles each. All four algorithms were quite robust to deviation from an idealized uniform allelic distribution, to departures from idealized Mendelian inheritance in simulated data sets and to the presence of null alleles. In contrast, none of the algorithms were very robust to the probable presence of error/mutation in the data. Depending upon the type of mutation or errors and the algorithm used, between 70 and 98% of the affected individuals were classified improperly on average.

Novel microsatellite markers and single nucleotide polymorphisms refine the tylosis with oesophageal cancer ( TOC ) minimal region on 17q25 to 42.5kb: sequencing does not identify the causative gene - Elisabeth J. Huckle; Lynn Rowbottom; Ian Dunham; Joanne E. Langan; Charlotte G. Cole; Joan M. Shaw; John K. Field; Irene M. Leigh; David P. Kelsell; Janet M. Risk; Fiona E. McRonald; Anthony Ellis; et al. (Human Genetics, 2004)

Temporal evolution of the European forest sector carbon sink from 1950 to 1999 - Gert‐Jan Nabuurs; Mart‐Jan Schelhaas; Godefridus (frits) M. J. Mohren; Christopher B. Field (Global Change Biology, 2003)
Estimates of the role of the European terrestrial biosphere in the global carbon cycle still vary by a factor 10. This is due to differences in methods and assumptions employed, but also due to difference in reference periods of the studies. The magnitude of the sink varies between years because of inter‐annual variation of short‐term climate, but also due to long‐term trends in development of the vegetation and its management. For this purpose, we present the results of an application of a carbon bookkeeping model to the forest sector of the European forests from 1950 to 1999. The analysis includes the compartments trees, soils, and wood products. The model uses statistics on European (30 countries excl. CIS) stemwood volume increment, forest area change, fellings, wood products and their international trade, and natural disturbances, supplemented with conversion coefficients, soil parameters and information on management. An (almost uninterrupted) increasing sink (Net Biome Production) in the European forest sector was found, increasing from 0.03 Pg C year −1 in the 1950s to 0.14 Pg C year −1 in the 1990s (for resp. 132 million hectares and 140 million hectares of forest). The sink in the tree and the soil compartment were approximately of the same size until 1970. After the 1970s the size of the sink in the tree biomass increases quickly, causing the tree biomass to account for some two thirds of the total sink in the 1990s. The results as presented here have to be regarded with caution especially with regard to the early decades of the analysis and with regard to the soil compartment.

Molecular diversity and characterization of nitrite reductase gene fragments ( nir K and nir S) from nitrate‐ and uranium‐contaminated groundwater - Tingfen Yan; Matthew W. Fields; Liyou Wu; Yuangang Zu; James M. Tiedje; Jizhong Zhou (Environmental Microbiology, 2003)
Summary Nitrate‐contaminated groundwater samples were analysed for nir K and nir S gene diversity. The samples differed with respect to nitrate, uranium, heavy metals, organic carbon content, pH and dissolved oxygen levels. A total of 958 nir K and 1162 nir S clones were screened by restriction fragment length polymorphism (RFLP) analysis: 48 and 143 distinct nir K and nir S clones, respectively, were obtained. A single dominant nir K restriction pattern was observed for all six samples and was 83% identical to the Hyphomicrobium zavarzinii nir K gene. A dominant nir S pattern was observed for four of the samples, including the background sample, and was 95% identical to the nir S of Alcaligenes faecalis. Diversity indices for nir K and nir S sequences were not related to any single geochemical characteristic, but results suggested that the diversity of nir K genes was inversely proportional to the diversity of nir S. Principal component analysis (PCA) of the sites based on geochemistry grouped the samples by low, moderate and high nitrate but PCA of the unique operational taxonomic units (OTUs) distributions grouped the samples differently. Many of the sequences were not closely related to previously observed genes and some phylogenetically related sequences were obtained from similar samples. The results indicated that the contaminated groundwater contained novel nir K and nir S sequences, functional diversity of both genes changed in relation to the contaminant gradient, but the nir K and nir S functional diversity was affected differently.

Root production and demography in a california annual grassland under elevated atmospheric carbon dioxide - Paul A. T. Higgins; Robert B. Jackson; Julia M. Des Rosiers; Christopher B. Field (Global Change Biology, 2002)
This study examined root production and turnover in a California grassland during the third year of a long‐term experiment with ambient (LO) and twice‐ambient atmospheric CO 2 (HI), using harvests, ingrowth cores, and minirhizotrons. Based on one‐time harvest data, root biomass was 32% greater in the HI treatment, comparable to the stimulation of aboveground production during the study year. However, the 30–70% increase in photosynthesis under elevated CO 2 for the dominant species in our system is considerably larger than the combined increase in above and belowground biomass. One possible explanation is, increased root turnover, which could be a sink for the additional fixed carbon. Cumulative root production in ingrowth cores from both treatments harvested at four dates was 2–3 times that in the single harvested cores, suggesting substantial root turnover within the growing season. Minirhizotron data confirmed this result, demonstrating that production and mortality occurred simultaneously through much of the season. As a result, cumulative root production was 54%, 47% and 44% greater than peak standing root length for the no chamber (X), LO, and HI plots, respectively. Elevated CO 2 , however, had little effect on rates of turnover (i.e. rates of turnover were equal in the LO and HI plots throughout most of the year) and cumulative root production was unaffected by treatment. Elevated CO 2 increased monthly production of new root length (59%) only at the end of the season (April–June) when root growth had largely ceased in the LO plots but continued in the HI plots. This end‐of‐season increase in production coincided with an 18% greater soil moisture content in the HI plots previously described. Total standing root length was not affected by CO 2 treatment. Root mortality was unaffected by elevated CO 2 in all months except April, in which plants grown in the HI plots had higher mortality rates. Together, these results demonstrate that root turnover is considerable in the grassland community and easily missed by destructive soil coring. However, increased fine root turnover under elevated CO 2 is apparently not a major sink for extra photosynthate in this system.

Mapping the free-swimming attack volume of a planktonic copepod, Euchaeta rimana - Doall M.; Strickler J.; Fields D.; Yen J. (Marine Biology, 2002)

Mapping the free-swimming attack volume of a planktonic copepod, Euchaeta rimana - Doall M.; Strickler J.; Fields D.; Yen J. (Marine Biology, 2002)

Reduction of humic substances by halorespiring, sulphate‐reducing and methanogenic microorganisms - Francisco J. Cervantes; Frank A. M. de Bok; Tuan Duong‐Dac; Alfons J. M. Stams; Gatze Lettinga; Jim A. Field (Environmental Microbiology, 2002)
Summary Physiologically distinct anaerobic microorganisms were explored for their ability to oxidize different substrates with humic acids or the humic analogue, anthraquinone‐2,6‐disulphonate (AQDS), as a terminal electron acceptor. Most of the microorganisms evaluated including, for example, the halorespiring bacterium, Desulfitobacterium PCE1, the sulphate‐reducing bacterium, Desulfovibrio G11 and the methanogenic archaeon, Methanospirillum hungatei JF1, could oxidize hydrogen linked to the reduction of humic acids or AQDS. Desulfitobacterium dehalogenans and Desulfitobacterium PCE1 could also convert lactate to acetate linked to the reduction of humic substances. Humus served as a terminal electron acceptor supporting growth of Desulfitobacterium species, which may explain the recovery of these microorganisms from organic rich environments in which the presence of chlorinated pollutants or sulphite is not expected. The results suggest that the ubiquity of humus reduction found in many different environments may be as a result of the increasing number of anaerobic microorganisms, which are known to be able to reduce humic substances.

Resource Optimization and Symbiotic Nitrogen Fixation - E. B. Rastetter; P. M. Vitousek; C. Field; G. R. Shaver; D. Herbert; G. I. gren (Ecosystems, 2001)

Middle Pleistocene interglacial deposits at Barling, Essex, England: evidence for a longer chronology for the Thames terrace sequence - D. R. Bridgland; R. C. Preece; H. M. Roe; R. M. Tipping; G. R. Coope; M. H. Field; J. E. Robinson; D. C. Schreve; K. Crowe (Journal of Quaternary Science, 2001)
Results are presented from a multidisciplinary study of fossiliferous interglacial deposits on the northern side of the Thames estuary. These fill a channel cut into London Clay bedrock and overlain by the Barling Gravel, a Thames–Medway deposit equivalent to the Lynch Hill and Corbets Tey Gravels of the Middle and Lower Thames, respectively. The channel sediments yielded diverse molluscan and ostracod assemblages, both implying fully interglacial conditions and a slight brackish influence. Pollen analysis has shown that the deposits accumulated during the early part of an interglacial. Plant macrofossils, particularly the abundance of Trapa natans , reinforce the interglacial character of the palaeontological evidence. A beetle fauna, which includes four taxa unknown in Britain at present, has allowed quantification of palaeotemperature using the mutual climatic range method ( T max 17 to 26 °C; T min −11 to 13 °C). A few vertebrate remains have been recovered from the interglacial deposits, but a much larger fauna, as well as Palaeolithic artefacts, is known from the overlying Barling Gravel. The age of the interglacial deposits is inferential. The geological context suggests a late Middle Pleistocene interglacial, part of the post‐diversion Thames system and therefore clearly post‐Anglian. This conclusion is supported by amino acid ratios from the shells of freshwater molluscs. The correlation of the overlying Barling Gravel with the Lynch Hill/Corbets Tey aggradation of the Thames valley constrains the age of the Barling interglacial to marine oxygen isotope stages 11 or 9. The presence of Corbicula fluminalis and Pisidium clessini confirms a pre‐Ipswichian (marine oxygen isotope substage 5e) age and their occurrence in the early part of the interglacial cycle at Barling precludes correlation with marine oxygen isotope stage 11, as these taxa occur only later in that interglacial at sites such as Swanscombe and Clacton. Thus by process of elimination a marine oxygen isotope stage 9 age would appear probable. Copyright © 2001 John Wiley & Sons, Ltd.

Two antagonistic functions of neural groups of the femoral chordotonal organ underlie thanatosis in the cricket Gryllus bimaculatus DeGeer - H. Nishino; M. Sakai; L. H. Field (Journal of Comparative Physiology A, 1999)

Sedimentology, palaeoecology and geochronology of Last Interglacial deposits from Deeping St James, Lincolnshire, England - D. H. Keen; M. D. Bateman; G. R. Coope; M. H. Field; H. E. Langford; J. S. Merry; T. M. Mighall (Journal of Quaternary Science, 1999)

Middle pleistocene interglacial sediments at Tye green, Stansted Airport, Essex, England - S. Boreham; M. H. Field; P. L. Gibbard (Journal of Quaternary Science, 1999)

Physical constraints of chemoreception in foraging copepods - Paul A. Moore; David M. Fields; Jeannette Yen (Limnology and Oceanography, 1999)
The small‐scale spatial and temporal dynamics of phycosphere‐sized chemical signals entrained within the feeding current of copepods is quantified here by combining flow visualization techniques with electrochemical technology (IVEC‐10). Using the 30‐ μ m electrochemical probe sampling at 50 Hz and the velocity gradients created by two marine copepods, we evaluated how odor deformation improves the potential for remote chemoreception. Our data show that when shear is strong, as found in the feeding current of an omnivore, Pleuromamma xiphias , elongation of the chemical signal is greater than that found for an odor signal entrained in the low‐shear feeding current of a carnivore, Euchaeta rimana . Furthermore, within the feeding current of a single species, E. rimana , certain areas provided greater potential for remote chemoreception. These results support the hypotheses that chemical signals are deformed by the feeding current and that the feeding current structure enhances signal detection. The deformation of the odor field within the laminar feeding current provides a leading edge that gives a chemosensitive copepod early warning of an approaching odor source. By sensing the leading edge, a copepod could have a few hundred milliseconds to reorient itself with respect to the odor source. Advance warning improves the probability of successful behavior in response to signal sources such as prey, predators, and mates.

Localization of a gene for incomplete X-linked congenital stationary night blindness to the interval between DXS6849 and DXS8023 in Xp11.23 - N. T. Bech-Hansen; Kym M. Boycott; Kathy J. Gratton; Daniel A. Ross; L. Leigh Field; William G. Pearce (Human Genetics, 1998)

A serological study of canine herpes virus-1 infection in the English dog population - M. J. Reading; H. J. Field (Archives of Virology, 1998)

Diet quality does not affect resting metabolic rate or body temperatures selected by an herbivorous lizard - K. E. Nussear; R. E. Espinoza; C. M. Gubbins; K. J. Field; J. P. Hayes (Journal of Comparative Physiology B, 1998)

B cell maturation and selection at the marrow-periphery interface - Michael P. Cancro; David M. Allman; Colleen E. Hayes; Vicky M. Lentz; Ryan G. Fields; Alex P. Sah; Mary Tomayko (Immunologic Research, 1998)

Middle Pleistocene temperate deposits at Dingé, Ille-et-Vilaine, northwest France: pollen, plant and insect macrofossil analysis - V. Andrieu; M. H. Field; P. Ponel; J. Guiot; P. Guenet; J.-L. de Beaulieu; M. Reille; M.-T. Morzadec-Kerfourn (Journal of Quaternary Science, 1997)

Enhanced performance of spatial and visual recognition memory tasks by the selective acetylcholinesterase inhibitor E2020 in rhesus monkeys - N. M. J. Rupniak; Spencer J. Tye; Mark J. Field (Psychopharmacology, 1997)

Middle Pleistocene deposits at Frog Hall Pit, Stretton‐on-Dunsmore, Warwickshire, English Midlands, and their implications for the age of the type Wolstonian - D. H. Keen; G. R. Coope; R. L. Jones; M. H. Field; H. I. Griffiths; S. G. Lewis; D. Q. Bowen (Journal of Quaternary Science, 1997)

Middle Pleistocene deposits at Frog Hall Pit, Stretton-on-Dunsmore, Warwickshire, English Midlands, and their implications for the age of the type Wolstonian - D. H. Keen; G. R. Coope; R. L. Jones; M. H. Field; H. I. Griffiths; S. G. Lewis; D. Q. Bowen (Journal of Quaternary Science, 1997)

Role and management of donkeys in samburu and turkana pastoralist societies in Northern Kenya - M. Twerda; D. Fielding; C. Field (Tropical Animal Health and Production, 1997)

Immunization with glycoprotein C of equine herpesvirus-1 is associated with accelerated virus clearance in a murine model - D. Tewari; S. V. Nair; M. C. De Ungria; G. L. Lawrence; M. Hayden; D. N. Love; H. J. Field; J. M. Whalley (Archives of Virology, 1995)

Enhanced biodegradation of aromatic pollutants in cocultures of anaerobic and aerobic bacterial consortia - Jim A. Field; Alfons J. M. Stams; Mario Kato; Gosse Schraa (Antonie van Leeuwenhoek, 1995)

The pathogenesis of wild type and drug resistant mutant strains of bovine herpesvirus-1 (BHV-1) in the natural host - S. E. Gilliam; A. M. Thackray; G. A. Brown; H. J. Field (Archives of Virology, 1993)

Alternative products from trees and shrubs to ?The role of trees in sustainable agriculture? conference, Albury, September 30th?October 3rd 1991 - A. Boutland; M. Robinson; J. Field; M. Scheltema; B. Hawkins; P. Bulman; J. Scarvelis; B. Mason; M. Wallace; M. Castley; P. A. Ryan; R. T. Henderson; et al. (Agroforestry Systems, 1992)

BK virus specific IgM responses in cord sera, young children and healthy adults detected by RIA - D. W. G. Brown; S. D. Gardner; P. E. Gibson; A. M. Field (Archives of Virology, 1984)

Zika virus infection of the central nervous system of mice - T. M. Bell; E. J. Field; H. K. Narang (Archives of Virology, 1971)

Influenzal encephalitis in mice - T. M. Bell; H. K. Narang; E. J. Field (Archives of Virology, 1971)